Toothed belt and its manufacturing method

The toothed belt achieves a balance between stiffness and flexibility through a layered rubber structure and high elastic modulus fibers, addressing issues of tooth chipping and jumping resistance under high-load conditions.

JP7661551B2Active Publication Date: 2025-04-14MITSUBOSHI BELTING LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024023084
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-03-10
Filing Date
2024-02-19
Publication Date
2025-04-14
Estimated Expiration
2044-02-19

AI Technical Summary

Technical Problem

Existing toothed belts struggle to achieve a balance between stiffness and flexibility, leading to issues such as tooth chipping and inadequate jumping resistance, especially under high-load conditions in rear-wheel drive applications of motorcycles.

Method used

The toothed belt features a layered structure with a first rubber layer and a second rubber layer, where the elastic modulus of the first rubber layer is greater than that of the second rubber layer. High elastic modulus fibers are used for the core wire, and short fibers are oriented along the contour of the tooth portion to enhance both rigidity and flexibility.

Benefits of technology

This design effectively improves tooth chipping resistance, suppresses jumping, and maintains tension and flexural fatigue resistance, even under high-load conditions, thereby extending the belt's lifespan.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661551000022
    Figure 0007661551000022
  • Figure 0007661551000023
    Figure 0007661551000023
  • Figure 0007661551000024
    Figure 0007661551000024
Patent Text Reader

Abstract

To provide a toothed belt which achieves rigidity and flexibility of tooth parts and is excellent in resistance to chipping of teeth.SOLUTION: A toothed belt 1 includes: a back part in which a core wire 5 extending in a circumferential direction of a belt is embedded; and a plurality of tooth parts formed on an inner peripheral surface of the back part at intervals in the belt circumferential direction. The toothed belt 1 further includes: a back rubber layer 6 formed at the belt outer periphery side relative to the core wire 5; and a first rubber layer 3 and a second rubber layer 4 formed at the belt inner periphery side relative to the core wire 5. The back part includes the back rubber layer 6. The tooth part is formed by the first rubber layer 3 and a second rubber layer 4 disposed between the first rubber layer 3 and the core wire 5. An elastic modulus of the first rubber layer 3 is adjusted so as to be larger than an elastic modulus of the second rubber layer 4. The first rubber layer 3 is formed by a first cross-linked rubber composition including a first rubber component of 100 mass part and first short fiber 3a of 5 to 60 mass parts. The core wire 5 is formed by a high elastic modulus fiber. The first short fibers 3a are aligned in a belt longitudinal direction along a contour of each tooth part.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a rubber toothed belt (or a rubber toothed belt covered with tooth cloth) that is useful for meshing with a toothed pulley to synchronously transmit power in motorcycles and the like under high load conditions, and to a method for manufacturing the same. [Background technology]

[0002] Power transmission belts that transmit power are broadly divided into friction power transmission belts and meshing power transmission belts. Examples of friction power transmission belts include flat belts, V-belts, and V-ribbed belts, while examples of meshing power transmission belts include toothed belts. Toothed belts have a back part in which a core wire is embedded approximately parallel to the belt circumferential direction, teeth parts arranged at a predetermined interval in the belt circumferential direction, and tooth cloth that covers the surface of the teeth parts. The teeth parts of the toothed belt transmit power by engaging with a pulley having a groove facing the teeth parts. Toothed belts do not slip between the pulley and can reliably transmit power even under high loads. In recent years, toothed belts have been increasingly used for industrial machines, internal combustion engines of automobiles, and rear-wheel drives of motorcycles, and in particular, toothed belts that are compatible with miniaturization (compatible with small-diameter pulleys, narrow width) are required as machines and vehicles are becoming smaller. If a miniaturized toothed belt is used in the same environment as a conventional large toothed belt, a higher load acts on the toothed belt. Therefore, there is a need for a toothed belt that is compact yet durable enough to withstand use under conditions of higher loads.

[0003] An important factor in the durability of a toothed belt is the rigidity (resistance to deformation) of the teeth. When the teeth are repeatedly deformed by contact with the toothed pulley during the meshing process with the toothed pulley, this leads to failures such as poor meshing due to tooth jumping and chipping due to cracks at the tooth base. Tooth chipping is a failure mode in which the teeth are removed from the belt body. It is believed that the mechanism is that, in the process in which stress is concentrated at the base of the teeth due to repeated deformation of the teeth, microcracks first occur at the tooth base and then grow. In particular, when a toothed belt is used under conditions of high load, the stress concentrated at the tooth base becomes particularly large, and cracks are likely to occur starting from the tooth base, leading to tooth chipping. In more detail, microcracks that occur mainly on the surface of the tooth part or near the surface of the tooth base often progress (grow) toward the inside of the tooth rubber that forms the tooth part, causing tooth chipping.

[0004] Therefore, it is necessary to increase the rigidity to suppress deformation of the teeth. On the other hand, increasing the rigidity of the teeth also increases the bending rigidity of the belt, decreasing flexibility. As toothed pulleys become smaller (smaller diameter) along with the miniaturization of machines and vehicles, high flexibility (suppleness) is also required to ensure good meshing when wound around a small diameter pulley. On the other hand, even if a microcrack does occur, tooth chipping can be prevented if the microcracks can be prevented from growing and leading to tooth chipping.

[0005] In other words, in a toothed belt, the rigidity (resistance to deformation) and flexibility (suppleness) of the teeth are in a trade-off relationship and it is difficult to achieve both. Therefore, a balanced formulation is required to achieve both, and if tiny cracks occur due to long-term use, it is necessary to suppress the growth of the cracks.

[0006] In particular, when a toothed belt is used for high-load transmission applications in rear-wheel drive of motorcycles, the width of the toothed belt is required to be narrowed in accordance with compactness. Therefore, in high-load transmission applications in rear-wheel drive of motorcycles, it is necessary to maintain meshing properties under high loads even when the width is narrowed, and ensure jumping resistance (high jumping torque). In addition, in high-load transmission applications in rear-wheel drive of motorcycles, jumping occurs due to a decrease in tension caused by belt elongation at the beginning of driving. Therefore, it is also necessary to ensure tension maintenance in order to suppress jumping at the beginning of driving. Furthermore, even in high-load transmission applications in rear-wheel drive of motorcycles, it is also necessary to ensure bending fatigue resistance in order to accommodate small-diameter pulleys.

[0007] JP 2021-188747 A (Patent Document 1) discloses that in order to improve the durability of toothed belts used for rear-wheel drive applications of motorcycles, the core wire extending in the longitudinal direction of the toothed belt and embedded in the belt is formed from a specific carbon fiber cord made by combining and twisting multiple under-twisted yarns containing carbon fiber.

[0008] JP 2023-18654 A (Patent Document 2) discloses a toothed belt having a tooth portion formed of a tooth cloth, a first rubber layer formed along the tooth cloth, and a second rubber layer formed between the first rubber layer and a core wire, in which the elastic modulus of the first rubber layer is adjusted to be greater than the elastic modulus of the second rubber layer. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Patent Publication No. 2021-188747 [Patent Document 2] JP 2023-18654 A Summary of the Invention [Problem to be solved by the invention]

[0010] However, in the toothed belt of Patent Document 1, it is difficult to achieve both rigidity and flexibility of the teeth of the toothed belt, and cracks are likely to occur. Furthermore, the resistance to tooth chipping is insufficient, and even if a crack occurs, it will immediately progress from the minute crack as a starting point and cause tooth chipping, so durability is also low.

[0011] Furthermore, the toothed belt of Patent Document 2 does not have sufficient resistance to tooth chipping and also does not have sufficient flexibility. If the toothed belt is used for rear wheel drive of a motorcycle and the width is narrowed, it is not possible to ensure jumping resistance, tension maintenance, and bending fatigue resistance.

[0012] Therefore, an object of the present invention is to provide a toothed belt that can achieve both rigidity (resistance to deformation) and flexibility (suppleness) in the tooth portion and is also excellent in resistance to tooth chipping (durability), and a method for manufacturing the same.

[0013] Another object of the present invention is to provide a toothed belt that can ensure jumping resistance, tension maintenance, and bending fatigue resistance even when narrowed in width for use in high-load transmission applications in rear-wheel drive of motorcycles, and a manufacturing method thereof. [Means for solving the problem]

[0014] In order to achieve the above object, the inventors have focused on the layer structure (allocation of mechanical properties) in the rubber layer constituting the tooth portion, and have studied intensively a well-balanced mode that can achieve both the rigidity (resistance to deformation) and flexibility (flexibility) of the tooth portion, which are in a trade-off relationship, while ensuring the rigidity of the tooth portion that can withstand use under conditions of higher load, and have also studied the compounding components of the rubber layer and the core wire in order to improve the tooth chipping resistance and suitability for rear-wheel drive applications of motorcycles. As a result, they have found that it is possible to achieve both the rigidity and flexibility of the tooth portion and improve the tooth chipping resistance by forming the tooth portion of a toothed belt with a first rubber layer and a second rubber layer formed between the first rubber layer and the core wire, adjusting the elastic modulus of the first rubber layer to be larger than that of the second rubber layer, forming the core wire with a high elastic modulus fiber, and compounding short fibers in the first rubber layer so as to be oriented in the belt longitudinal direction along the contour of the tooth portion, thereby completing the present invention.

[0015] That is, the toothed belt according to embodiment [1] of the present invention is as follows: A back portion in which a core wire extending along a circumferential direction of the belt is embedded; A plurality of teeth are formed on an inner circumferential surface of the back portion at intervals in a belt circumferential direction, A toothed belt including a back rubber layer formed on the outer circumferential side of the belt with respect to the core wire, and a first rubber layer and a second rubber layer formed on the inner circumferential side of the belt with respect to the core wire, The back portion includes the back rubber layer, the elastic modulus of the first rubber layer is greater than the elastic modulus of the second rubber layer, the first rubber layer is formed of a first crosslinked rubber composition containing a first rubber component and a first short fiber, a ratio of the first short fibers is 5 to 60 parts by mass with respect to 100 parts by mass of the first rubber component, The first short fibers are oriented in the belt longitudinal direction along the contour of the tooth portion, the core wire comprises high modulus fibers; and The tooth portion includes the first rubber layer and the second rubber layer interposed between the first rubber layer and the core wire.

[0016] Aspect [2] of the present invention is an aspect of aspect [1], in which the area ratio of the first rubber layer is 10 to 80 area % of the total area of ​​the first rubber layer and the second rubber layer in a cross-sectional view in the circumferential direction of the belt.

[0017] Aspect [3] of the present invention is an aspect of aspect [1] or [2], wherein the first rubber layer has a tensile strength in the belt circumferential direction of 40 to 90 MPa, a tensile modulus in the belt width direction of 4 to 25 MPa, the second rubber layer has a tensile strength in the belt circumferential direction of 10 to 50 MPa, and a tensile modulus in the belt width direction of 1 to 10 MPa.

[0018] Aspect [4] of the present invention is any one of aspects [1] to [3] above, wherein the tensile modulus of elasticity in the belt width direction of the first rubber layer is 1.1 to 10 times the tensile modulus of elasticity in the belt width direction of the second rubber layer.

[0019] The aspect [5] of the present invention is any one of the aspects [1] to [4], wherein the first short fibers are polyamide fibers.

[0020] Aspect [6] of the present invention is any one of aspects [1] to [5], The first crosslinked rubber composition further comprises a first crosslinking agent and a first co-crosslinking agent, the second rubber layer is formed of a second crosslinked rubber composition containing a second rubber component, a second crosslinking agent, and a second co-crosslinking agent; The first rubber component includes a first composite polymer including a hydrogenated nitrile rubber and an unsaturated carboxylic acid metal salt, The second rubber component includes a second composite polymer including a hydrogenated nitrile rubber and an unsaturated carboxylate metal salt, A ratio of the first co-crosslinking agent is 1 to 40 parts by mass with respect to 100 parts by mass of the first rubber component, and In this embodiment, the ratio of the second co-crosslinking agent is 0.2 to 25 parts by mass with respect to 100 parts by mass of the second rubber component.

[0021] Aspect [7] of the present invention is an aspect of aspect [6], wherein the second crosslinked rubber composition further contains second short fibers, and the proportion of the second short fibers in the second crosslinked rubber composition is 5 parts by mass or less per 100 parts by mass of the second rubber component.

[0022] The present invention relates to an embodiment [8] of the present invention, in the above embodiment [6] or [7], The first crosslinked rubber composition further comprises a first reinforcing inorganic filler, The second crosslinked rubber composition further comprises a second reinforcing inorganic filler, A ratio of the first composite polymer in the first rubber component is 80% by mass or more, A ratio of the second composite polymer in the second rubber component is 30% by mass or more, the first crosslinking agent contains a first organic peroxide, and a ratio of the first organic peroxide is 1 to 20 parts by mass with respect to 100 parts by mass of the first rubber component; the second crosslinking agent contains a second organic peroxide, and a ratio of the second organic peroxide is 0.5 to 5 parts by mass with respect to 100 parts by mass of the second rubber component; A ratio of the first reinforcing inorganic filler is 10 parts by mass or less based on 100 parts by mass of the first rubber component, and In this embodiment, the ratio of the second reinforcing inorganic filler is 10 parts by mass or less based on 100 parts by mass of the second rubber component.

[0023] An embodiment [9] of the present invention is any one of the above embodiments [1] to [8], wherein the value X of the arrangement density of the core wires is 5 to 25%.

[0024] Aspect

[10] of the present invention is any one of aspects [1] to [9], The tooth pitch of the tooth portion is 6 to 16 mm, When the tooth pitch is 6 mm or more and less than 9.5 mm, the belt elastic modulus is 15 to 20 kN / mm; When the tooth pitch is 9.5 mm or more and less than 12.5 mm, the belt elastic modulus is 42 to 60 kN / mm; and When the tooth pitch is 12.5 to 16 mm, the belt elastic modulus is 50 to 65 kN / mm.

[0025] An embodiment

[11] of the present invention is a toothed belt transmission mechanism equipped with the toothed belt of any one of the embodiments [1] to

[10] , wherein the toothed belt is a toothed belt transmission mechanism used for power transmission in rear wheel drive of a motorcycle.

[0026] The present invention also includes, as aspect

[12] , a method for producing a toothed belt according to any of the aspects [1] to

[11] , comprising: a first-rubber-layer-preparation step of preparing an uncrosslinked rubber sheet having first short fibers oriented in one direction of the sheet surface as a first-rubber-layer precursor for forming a first rubber layer; and a pre-molding step of laminating the first rubber layer precursor and a second rubber layer precursor, which is an uncrosslinked rubber sheet for forming a second rubber layer, in an arrangement in which the first short fibers are oriented in the longitudinal direction of the belt, to produce a pre-molded body in a semi-crosslinked state.

[0027] In the present application, a numerical range expressed as "A to B" means "A or more and B or less," and is used in the sense that both ends, A and B, are included. Effect of the Invention

[0028] In the present invention, the toothed belt is formed of a first rubber layer and a second rubber layer formed between the first rubber layer and the core wire, the elastic modulus of the first rubber layer is adjusted to be larger than that of the second rubber layer, the first rubber layer is formed of a first crosslinked rubber composition containing 100 parts by mass of a first rubber component and 5 to 60 parts by mass of a first short fiber, and the core wire contains a high elastic modulus fiber, and the first short fiber is oriented in the belt longitudinal direction along the contour of the toothed belt (the contour of the first rubber layer or the tooth cloth surface). Therefore, while ensuring the rigidity of the toothed belt that can withstand use under conditions where a higher load is applied, the rigidity and flexibility of the toothed belt, which are in a trade-off relationship, can be achieved, and the tooth chipping resistance can be improved. Therefore, in the present invention, a toothed belt can be provided that can suppress jumping (tooth skipping) during belt running and also improve belt durability. In this toothed belt, loss of the toothed belt (tooth chipping) due to the growth of microcracks occurring during running can also be suppressed, and a long life can be achieved during high-load running. In particular, the toothed belt of the present invention can ensure jumping resistance, tension maintenance, and flexural fatigue resistance even when narrowed for use in high load transmission applications in rear wheel drive of motorcycles. [Brief description of the drawings]

[0029] [Figure 1] FIG. 1 is a partial cross-sectional perspective view showing an example of a toothed belt according to the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of the toothed belt of FIG. [Diagram 3] FIG. 3 is a schematic cross-sectional view for explaining the function of the toothed portion of the toothed belt of FIG. [Figure 4] FIG. 4 is a schematic cross-sectional view for explaining the orientation state of short fibers in the toothed belt of FIG. [Diagram 5] FIG. 5 is a schematic cross-sectional view for explaining a state in which a crack occurs in a toothed belt. [Figure 6] FIG. 6 is a schematic diagram for explaining a method for measuring the X value (%) of the array density. [Figure 7] FIG. 7 is a schematic diagram for explaining a measuring method for the tooth rigidity test in the examples. [Figure 8]FIG. 8 is a graph showing an example of measurement data for explaining the measurement method of the tooth stiffness test of the embodiment. [Figure 9] FIG. 9 is a schematic cross-sectional view of a toothed portion of a toothed belt obtained in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] <Toothed belt> Hereinafter, an example of the toothed belt of the present invention will be described in detail with reference to the accompanying drawings as necessary.

[0031] FIG. 1 is a partial cross-sectional perspective view showing an example of a toothed belt of the present invention, and FIG. 2 is a schematic cross-sectional view of the toothed belt of FIG. 1. The toothed belt 1 of this example is an endless meshing power transmission belt, and includes a back portion 1c in which a core wire 5 extending in the belt circumferential direction (longitudinal direction) is embedded, and a plurality of teeth 1a provided at a predetermined interval on the inner peripheral surface of the back portion 1c and extending in the belt width direction, and the belt surface (inner peripheral surface) on the tooth portion side is composed of a tooth cloth 2. The back portion 1c has a back rubber layer 6 arranged on the belt outer peripheral surface side of the core wire 5, and this back rubber layer 6 forms the belt outer peripheral surface. Furthermore, the toothed belt 1 of the present invention has a first rubber layer (surface rubber layer) 3 and a second rubber layer (inner rubber layer) 4 between the tooth cloth 2 and the core wire 5 on the belt inner peripheral surface side of the core wire 5. The first rubber layer 3 is disposed on the inner circumferential surface of the belt along the contour of the tooth cloth 2 (in contact with the tooth cloth 2), and the second rubber layer 4 is interposed or disposed between the first rubber layer 3 and the core wires 5 (in contact with the core wires 5). The first rubber layer 3 has a higher elastic modulus (particularly, a tensile elastic modulus) than the second rubber layer 4.

[0032] Between adjacent tooth portions 1a, flat tooth bottom portions 1b are present, and the tooth portions 1a and the tooth bottom portions 1b are alternately formed along the circumferential direction (belt longitudinal direction) on the inner peripheral surface of the belt. That is, the surface of the tooth portions 1a and the inner peripheral surface of the back portion 1c (i.e., the surface of the tooth bottom portions 1b) are formed of a single continuous tooth cloth 2.

[0033] In the embodiment shown in Fig. 1, the tooth cloth constituting the surface of the tooth part is a constituent element of the tooth part, while the tooth cloth constituting the surface of the tooth bottom part is a constituent element of the back part. Also, each tooth cloth constituting the tooth part is a part of a continuous tooth cloth (a part of tooth cloth 2 in Fig. 2).

[0034] In this example, the tooth portion 1a has a substantially trapezoidal cross section in the circumferential direction of the belt. The tooth portion 1a having a substantially trapezoidal cross section has a circumferential surface made of the tooth cloth 2, and is formed of a first rubber layer 3 formed along the tooth cloth 2 and a second rubber layer 4 formed between the first rubber layer 3 and the core wire 5. That is, in the tooth portion 1a, the first rubber layer 3 is a layer formed along the tooth cloth 2, and the second rubber layer 4 is a layer formed between the first rubber layer 3 and the core wire 5.

[0035] In the tooth bottom portion 1b as well, a first rubber layer as a surface rubber layer and a second rubber layer as an inner rubber layer (not shown) are interposed between the tooth cloth 2 and the core wire 5. The thicknesses of the first and second rubber layers in the tooth bottom portion are extremely thinner than the thicknesses of the first and second rubber layers 3 and 4 in the tooth portion 1a.

[0036] The cords 5 extend in the belt longitudinal direction (circumferential direction) and are arranged at intervals in the belt width direction. The gaps between adjacent cords 5 may be formed by the crosslinked rubber composition constituting the back rubber layer 6 and / or the second rubber layer (particularly the crosslinked rubber composition constituting the back rubber layer 6).

[0037] Toothed belts are used for high-load transmission applications in industrial machines, internal combustion engines of automobiles, rear-wheel drives of motorcycles, etc., and are preferably used for high-load transmission applications in rear-wheel drives of motorcycles. For example, when a toothed belt is wound between a driving pulley (toothed pulley) and a driven pulley (toothed pulley), the belt transmits power from the driving pulley to the driven pulley by the rotation of the driving pulley.

[0038] The toothed belt of the present invention is not limited to the form and structure shown in Figures 1 and 2. For example, the multiple toothed portions may be capable of meshing with a toothed pulley, and the cross-sectional shape of the toothed portions (cross-sectional shape of the toothed belt in the belt circumferential direction) is not limited to a substantially trapezoidal shape, and may be, for example, a semicircular shape, a semi-elliptical shape, or a polygonal shape [a triangular shape, a quadrilateral (rectangular shape, trapezoidal shape, etc.)]. Of these, a trapezoidal shape or a substantially trapezoidal shape is preferable from the viewpoint of meshing power transmission, etc.

[0039] In the toothed belt (inner peripheral side of the core wire) of the present invention, the area ratio of the first rubber layer is, for example, 10 to 80 area%, preferably 20 to 70 area%, more preferably 30 to 60 area%, and even more preferably 35 to 50 area% of the total area of ​​the first rubber layer and the second rubber layer in a cross-sectional view in the belt circumferential direction (belt longitudinal direction). If this area ratio is too small, the rigidity (resistance to deformation) of the teeth may be insufficient, whereas if it is too large, the bending rigidity of the belt may be high and the flexibility (suppleness) may be insufficient.

[0040] In the toothed belt of the present invention, the average distance between the centers of adjacent teeth in the circumferential direction (tooth pitch, see FIG. 2) may be, for example, 2 to 25 mm depending on the shape of the toothed pulley. The value of the tooth pitch also corresponds to the size of the scale of the toothed portion (the length of the toothed portion in the belt circumferential direction and the tooth height of the toothed portion). That is, the larger the tooth pitch, the larger the scale of the toothed portion becomes. In particular, in applications where a high load acts, a toothed portion with a large scale is required, and the tooth pitch may be 5 mm or more, and preferably 8 mm or more. The tooth pitch can be appropriately selected depending on the application, and may be 6 to 16 mm, for example, about 8 to 14 mm (particularly 10 to 14 mm), for transmission applications in rear wheel drive of motorcycles. In the present invention, as described later, the elastic modulus of the toothed belt can be controlled by adjusting the material (elastic modulus), twist coefficient, diameter, pitch, and arrangement density of the core wire depending on the tooth pitch, and a toothed belt suitable for high load transmission applications in rear wheel drive of motorcycles can be manufactured.

[0041] Furthermore, the average tooth height of the toothed portion is preferably 40 to 70%, and more preferably 50 to 65%, of the average thickness of the entire belt.

[0042] In the present application, as shown in FIG. 2, the average tooth height of the teeth means the average height of the protruding teeth on the inner circumferential surface of the belt (the average height of the teeth protruding from the tooth bottom).

[0043] [Tooth] The toothed portion includes a first rubber layer disposed on the surface side (inner surface side) and a second rubber layer disposed on the inner side in contact with the first rubber layer. The first rubber layer and the second rubber layer are formed of crosslinked rubber compositions having different compositions, and the elastic modulus (modulus) of the first rubber layer is relatively large, and the elastic modulus (modulus) of the second rubber layer is relatively small. In the toothed belt of the present invention, the crosslinked rubber composition forming the toothed portion has such a two-layer structure, so that the rigidity and flexibility of the toothed portion can be compatible. This mechanism will be explained with reference to FIG. 3. In the present application, the rubber layer forming the toothed portion means a rubber layer interposed between the core wire and the tooth cloth when the toothed portion includes a tooth cloth, and means a rubber layer interposed on the inner peripheral surface side of the core wire when the toothed portion does not include a tooth cloth. The first rubber layer and the second rubber layer, which are the rubber layers forming the toothed portion, are collectively referred to as tooth rubber layers. In the tooth rubber layer, the first rubber layer is a layer consisting of a single phase formed from a first crosslinked rubber composition, and the second rubber layer is a layer consisting of a single phase formed from a second crosslinked rubber composition.

[0044] The tooth portion may further include a tooth cloth forming a surface. When the tooth portion does not include a tooth cloth, the surface of the first rubber layer forms the inner circumferential surface of the belt, but when the tooth portion includes a tooth cloth, the surface of the tooth rubber layer is covered with the tooth cloth and the inner circumferential surface of the belt is formed of the tooth cloth. In other words, when the tooth portion includes a tooth cloth, the tooth portion includes a first rubber layer whose surface is formed of the tooth cloth and disposed along the contour of the tooth portion on the surface side in contact with the tooth cloth, and a second rubber layer disposed on the inner side in contact with the first rubber layer.

[0045] The inventors have found that the part inside the tooth portion that affects flexibility (suppleness) is the inside of the tooth portion corresponding to the second rubber layer, particularly part C located below the core wire 5. That is, they have found that if the inside of the tooth portion, particularly part C, is a rubber layer with high rigidity (high elastic modulus), flexibility (suppleness) decreases. Therefore, in the toothed belt of the present invention, in order to ensure high flexibility, the second rubber layer located inside the tooth portion, particularly the second rubber layer 4 having part C therein, is adjusted to have a relatively low rigidity (low elastic modulus).

[0046] Furthermore, the inventors have found that the portion inside the tooth portion that affects the deformation resistance is the vicinity of the tooth cloth (or inner peripheral surface) corresponding to the first rubber layer, particularly the portion A located on the side of the tooth portion and the portion B located near the tooth bottom. That is, they have found that if the portions A and B are rubber layers with low rigidity (low elastic modulus), the deformation resistance decreases. In detail, the portion A, which is the side of the tooth portion, is the portion that comes into contact with the pulley and receives the most load (impact), so it is effective if the crosslinked rubber composition of the portion A has high rigidity (high elastic modulus). On the other hand, the portion B, which is the base near the tooth bottom, is the portion where minute cracks first occur (the starting point leading to tooth chipping) due to repeated deformation, so it is effective if the crosslinked rubber composition of the portion B has high rigidity (high elastic modulus). Therefore, in the toothed belt of the present invention, in order to ensure the deformation resistance, the first rubber layer 3 containing the portions A and B is adjusted to have a relatively high rigidity (high elastic modulus).

[0047] From the viewpoint of deformation resistance, it is sufficient that at least parts A and B of the tooth portion are made of high rigidity rubber, and the top portion (tooth tip portion) of the tooth portion does not have to be made of high rigidity rubber. In contrast, in the toothed belt of the present invention, the first rubber layer including the top portion is made of high rigidity rubber because it is highly productive and can achieve a high degree of deformation resistance.

[0048] The tensile strength of the first rubber layer in the circumferential direction of the belt is, for example, 40 to 90 MPa, preferably 45 to 85 MPa, further preferably 50 to 83 MPa, more preferably 55 to 80 MPa, and most preferably 60 to 70 MPa. If the tensile strength is too small, the rigidity of the teeth portion may decrease, and the deformation resistance may decrease. Conversely, if the tensile strength is too large, the flexibility of the belt, in particular, the winding (meshing) ability around a small diameter pulley may decrease.

[0049] The tensile strength of the second rubber layer in the circumferential direction of the belt is, for example, 10 to 50 MPa, preferably 20 to 45 MPa, further preferably 25 to 40 MPa, more preferably 25 to 35 MPa, and most preferably 30 to 34 MPa. If the tensile strength is too small, the deformation resistance may decrease, whereas if it is too large, the flexibility of the belt, in particular the winding (meshing) ability around a small diameter pulley, may decrease.

[0050] In the circumferential direction of the belt, the tensile strength of the first rubber layer is greater than that of the second rubber layer, and the ratio of the tensile strength of the first rubber layer to that of the second rubber layer (tensile strength of the first rubber layer / tensile strength of the second rubber layer) may be 1.3 to 3.5, preferably 1.4 to 3.0, further preferably 1.5 to 2.5, more preferably 1.6 to 2.0, and most preferably 1.7 to 1.9. By setting the ratio of the tensile strengths of both layers within this range, a balance can be achieved between the rigidity (resistance to deformation) and flexibility (suppleness) of the tooth portion, which are in a trade-off relationship, and both can be achieved.

[0051] In the present application, the tensile strength of the first rubber layer and the second rubber layer is determined by the "tensile strength T" of each rubber layer, which can be measured by a method conforming to JIS K 6251 (2017). In detail, the tensile strength can be measured by the method described in the examples below.

[0052] The tensile modulus of the first rubber layer in the belt width direction can be selected from the range of, for example, about 4 to 25 MPa, and is, for example, 5 to 20 MPa, preferably 6 to 18 MPa, further preferably 8 to 16 MPa, more preferably 10 to 15 MPa, and most preferably 12 to 15 MPa. If the tensile modulus is too small, the rigidity of the teeth portion may decrease, and the deformation resistance may decrease. Conversely, if it is too large, the flexibility of the belt, in particular the winding (meshing) ability around a small diameter pulley, may decrease.

[0053] The tensile modulus of the second rubber layer in the belt width direction is, for example, 1.0 to 10.0 MPa, preferably 1.5 to 5.0 MPa, further preferably 1.6 to 4.0 MPa, more preferably 1.8 to 3.0 MPa, and most preferably 1.9 to 2.5 MPa. If the tensile modulus is too small, there is a risk that the deformation resistance will decrease, whereas if it is too large, there is a risk that the flexibility of the belt, in particular the winding (meshing) ability around a small diameter pulley, will decrease.

[0054] In the belt width direction, the tensile modulus of the first rubber layer is greater than that of the second rubber layer, and the ratio of the tensile modulus of the first rubber layer to the tensile modulus of the second rubber layer (tensile modulus of the first rubber layer / tensile modulus of the second rubber layer) may be 1.1 to 15.0, for example, 1.1 to 10.0, preferably 2.0 to 10.0, more preferably 4.0 to 9.5, more preferably 5.0 to 9.0 (for example, 5.5 to 8.5), even more preferably 6.0 to 8.0, and most preferably 6.0 to 7.5. By setting the ratio of the tensile moduli of both layers within this range, the rigidity (resistance to deformation) and flexibility (flexibility) of the tooth portion, which are in a trade-off relationship, can be balanced and both can be achieved.

[0055] In the present application, the tensile modulus of the first rubber layer and the second rubber layer is determined by the "tensile stress at 2% elongation" of each rubber layer, which can be measured by a method conforming to JIS K 6251 (2017). In detail, the tensile modulus can be measured by the method described in the examples below.

[0056] Furthermore, in the tooth portion, the first rubber layer is formed of a first crosslinked rubber composition containing a first rubber component and a first short fiber, and the first short fiber is oriented in the belt longitudinal direction (belt circumferential direction) along the contour of the tooth portion. In the toothed belt of the present invention, by adjusting the tooth portion to a two-layer structure as described above, it is possible to achieve both rigidity and flexibility, and to suppress microcracks that mainly occur at the tooth base. Even if microcracks occur due to long-term use, the first short fiber is oriented in the above direction in the first rubber layer, so that the toothed belt is prevented from leading to tooth chipping, and the tooth chipping resistance (durability) of the belt can be improved. The mechanism by which tooth chipping resistance is improved will be described with reference to Figs. 4 and 5.

[0057] FIG. 4 is a schematic cross-sectional view for explaining the orientation state of short fibers in the toothed belt of FIG. 1, and FIG. 5 is a schematic cross-sectional view for explaining a state in which a crack has occurred in the toothed belt.

[0058] 5, the toothed belt 11 is formed of a tooth cloth 12, a tooth rubber layer 13 covered with the tooth cloth 12, a back rubber layer 16, and a core wire 15 interposed between the tooth rubber layer 13 and the back rubber layer 16, and microcracks are likely to occur on the rubber surface at the base of the teeth of the tooth rubber layer 13 or near the surface. The generated microcracks progress from the rubber surface toward the inside of the tooth rubber layer 13 in a direction approximately perpendicular to the surface (the direction of arrow A in FIG. 5), growing into cracks 13a and resulting in chipped teeth.

[0059] In contrast, as shown in Fig. 4, in the toothed belt 1 of the present invention, the first rubber layer 3 located on the tooth cloth 2 side contains first short fibers 3a. Fig. 4 is a diagram showing a schematic distribution state of the first short fibers 3a in the first rubber layer 3 for understanding the orientation direction of the first short fibers 3a, and in the first rubber layer 3, the first short fibers 3a are oriented in the belt longitudinal direction along the contour of the tooth cloth 2 (the surface direction of the tooth cloth). That is, in the first rubber layer 3, the first short fibers 3a are oriented approximately parallel to the surface direction of the tooth cloth. The orientation direction of the first short fibers 3a is a direction intersecting (particularly, substantially perpendicular) to the direction in which microcracks progress (a direction extending inward from the tooth cloth surface, such as the direction of arrow A in FIG. 5, or a direction substantially perpendicular to the tooth cloth surface). Therefore, when the first rubber layer 3 contains the first short fibers 3a at a predetermined ratio, the first short fibers 3a are always present in the direction in which microcracks occur on the surface or inside of the first rubber layer 3, intersecting or substantially perpendicular to the direction of progress of the microcracks. Therefore, in the first rubber layer 3 of the toothed belt 1 of the present invention, the first short fibers 3a have a function of preventing (guarding) the progress of microcracks, and even if microcracks occur due to repeated deformation, the progress of the cracks can be prevented, and the tooth chipping resistance of the toothed belt can be improved. The ratio of the first short fibers to exhibit such a function is about 5 to 60 parts by mass, particularly about 10 to 60 parts by mass, relative to 100 parts by mass of the first rubber component. In contrast, in a toothed belt in which the tooth rubber layer contains a small proportion of short fibers, the progression of cracks cannot be effectively prevented, and resistance to tooth chipping cannot be improved. In addition, the moduli of the tooth rubber layer and the adhesive rubber layer are not adjusted, and microcracks are also likely to occur.

[0060] In the present application, the state in which the first short fibers are oriented along the contour of the tooth portion means not only the state in which the first short fibers are oriented substantially parallel to the contour of the tooth portion but also the state in which the first short fibers are oriented substantially parallel to the contour of the tooth cloth (or the inner circumferential surface), and also the state in which the first short fibers are oriented in the belt longitudinal direction.

[0061] In the present application, the "contour of the tooth portion" may be the contour of the first rubber layer, or if the tooth portion includes a tooth cloth, may be the surface of the tooth cloth or the interface between the tooth cloth and the first rubber layer, or may be the interface between the first rubber layer and the second rubber layer. In particular, whether or not the first short fiber is oriented along the contour of the tooth portion may be determined based on the interface between the first rubber layer and the second rubber layer, and it may be determined that the first short fiber is oriented along the contour of the tooth portion if the first short fiber is approximately parallel to the corresponding interface (the corresponding portion of the interface that is the shortest distance from the first short fiber).

[0062] The shape of the first rubber layer is not particularly limited as long as it is a layer formed along the tooth cloth, and is not limited to the layer shapes having a non-uniform thickness shown in Figures 1 to 3 (i.e., a shape in which the layer thickness is maximum at the top or center of the tooth portion and decreases toward the bottom of the tooth portion in a cross section of the tooth portion in the belt longitudinal direction), but may be a layer shape having a uniform thickness. Among these, from the viewpoint of productivity, etc., a layer shape having a non-uniform thickness (particularly, a shape in which the layer thickness is maximum at the top or center of the tooth portion and decreases toward the bottom of the tooth portion in a cross section of the tooth portion in the belt longitudinal direction) is preferable.

[0063] In the tooth portion, the area ratio of the first rubber layer can be selected from the range of about 5 to 85 area% of the total area of ​​the first rubber layer and the second rubber layer in the cross section of the belt longitudinal direction (circumferential direction), for example, 10 to 80 area%, preferably 20 to 70 area%, more preferably 30 to 60 area%, and more preferably 35 to 50 area%. If this area ratio is too small, the rigidity (resistance to deformation) of the tooth portion is insufficient, and the running property and durability of the belt may be deteriorated, and conversely, if it is too large, the bending rigidity of the belt becomes high, the flexibility (flexibility) is insufficient, and the durability of the belt may be deteriorated. In applications where the durability of the belt is important, the area ratio is preferably 15 to 65 area%, more preferably 20 to 60 area%.

[0064] The shape of the second rubber layer is not limited to a substantially trapezoidal shape formed between the first rubber layer and the core wire in a cross section of the tooth portion in the belt longitudinal direction, but may be a layer formed along the first rubber layer, a substantially trapezoidal shape formed between the core wire and another rubber layer formed along the first rubber layer, etc. Among these, from the viewpoint of improving the flexibility of the tooth portion, a shape in contact with the core wire, i.e., a substantially trapezoidal shape formed between the first rubber layer and the core wire, and a substantially trapezoidal shape formed between the other rubber layer and the core wire are preferred, and a substantially trapezoidal shape formed between the first rubber layer and the core wire is particularly preferred.

[0065] The rubber hardness Hs of the first rubber layer (first crosslinked rubber composition constituting the first rubber layer) is, for example, 65 to 80 degrees, preferably 68 to 78 degrees, more preferably 70 to 76 degrees, and most preferably 72 to 74 degrees, in type D hardness. If the hardness is too low, the rigidity of the teeth may decrease, resulting in a decrease in deformation resistance, whereas if the hardness is too high, the flexibility of the belt, particularly the winding (meshing) ability around a small diameter pulley, may decrease.

[0066] The rubber hardness Hs of the second rubber layer (the second crosslinked rubber composition constituting the second rubber layer) is, for example, 50 to 66 degrees, preferably 53 to 65 degrees, further preferably 54 to 62 degrees, further preferably 55 to 60 degrees, and most preferably 56 to 59 degrees, in type D hardness. If the hardness is too low, there is a risk of the deformation resistance decreasing, whereas if the hardness is too high, there is a risk of the flexibility of the belt, particularly the durability against reverse bending decreasing.

[0067] In the present application, the type D hardness of the first rubber layer and the second rubber layer indicates a value Hs (type D) measured using a type D durometer in accordance with the spring type durometer hardness test specified in JIS K 6253 (2012) (vulcanized rubber and thermoplastic rubber - Determination of hardness) and may be simply referred to as rubber hardness. In detail, it can be measured by the method described in the examples below, and can be measured as the hardness of a rubber sheet obtained by crosslinking the rubber composition for forming the belt.

[0068] Usually, type A hardness (value measured using a type A durometer) is often used for the rubber hardness of a rubber composition, but when the value measured using a type A durometer exceeds 90 degrees, it is considered desirable to use a type D durometer. In the toothed belt of the present invention, the hardness of the rubber layer constituting the tooth portion is higher than the hardness of the back rubber layer described below, and the type A hardness exceeds 90 degrees. Therefore, the hardness of the rubber layer constituting the tooth portion is evaluated using type D hardness.

[0069] The tooth portion may further include another rubber layer as the tooth rubber layer in addition to the first rubber layer and the second rubber layer, as long as the effect of the present invention is not impaired. Examples of the other rubber layer include an adhesive rubber layer interposed between the tooth cloth and the first rubber layer, and an intermediate rubber layer interposed between the first rubber layer and the second rubber layer. The adhesive rubber layer may be a layer for improving the adhesion between the tooth cloth and the first rubber layer. The intermediate rubber layer may be a layer having a tensile modulus smaller than that of the first rubber layer and larger than that of the second rubber layer. Among these, the adhesive rubber layer (third rubber layer) is preferred. The thickness of the adhesive rubber layer may be such that it is possible to improve the adhesion between the tooth cloth and the first rubber layer. Specifically, the thickness of the third rubber layer (adhesive rubber layer) is preferably 0.5 mm or less, more preferably 0.3 mm or less, at the top of the tooth portion. If the thickness of the third rubber layer is too thick, the rigidity of the tooth portion may be reduced.

[0070] As for the structure of the tooth portion, a structure in which the tooth rubber layer includes only an adhesive rubber layer as the other layer is preferred, and a structure including no other layers, i.e., a structure consisting of a first rubber layer and a second rubber layer formed between this first rubber layer and the core wire, or a structure consisting of a tooth cloth covering the circumferential surface of the belt, a first rubber layer formed along the tooth cloth, and a second rubber layer formed between this first rubber layer and the core wire, is particularly preferred.

[0071] (Crosslinked Rubber Composition) In the toothed belt of the present invention, the first rubber layer is characterized by being formed of a first crosslinked rubber composition containing the first short fiber as an essential component, but both the first rubber layer and the second rubber layer may be formed of a crosslinked rubber composition commonly used as a rubber composition for toothed belts. The crosslinked rubber composition may be a crosslinked rubber composition containing a rubber component, and by appropriately adjusting the composition of the composition, it is possible to adjust the mechanical properties such as the modulus of elasticity of each layer constituting the rubber layer, particularly the first rubber layer and the second rubber layer. The method of adjusting the modulus of elasticity, etc. is not particularly limited, and may be adjusted by changing the composition and / or type of the components constituting the composition, and from the viewpoint of simplicity, etc., it is preferable to adjust by changing the ratio and / or type of the crosslinked compounding agent, short fiber, and filler.

[0072] (A) Rubber component Examples of the rubber components (first rubber component and second rubber component) of the crosslinked rubber composition forming the first rubber layer and the second rubber layer include diene rubbers [natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), chloroprene rubber (CR), butyl rubber (IIR), styrene-butadiene rubber (SBR), vinylpyridine-styrene-butadiene rubber, acrylonitrile-butadiene rubber (nitrile rubber: NBR), acrylonitrile-chloroprene rubber, hydrogenated nitrile rubber (HNBR), etc.], ethylene-α-olefin elastomers (ethylene-propylene copolymer (EPM), ethylene-propylene-diene terpolymer (EPDM), etc.), chlorosulfonated polyethylene rubber (CSM), alkylated chlorosulfonated polyethylene rubber (ACSM), epichlorohydrin rubber, acrylic rubber, silicone rubber, urethane rubber, fluororubber, etc. These rubber components may be carboxylated, such as carboxylated SBR and carboxylated NBR. These rubber components may be used alone or in combination.

[0073] A particularly preferred rubber component is hydrogenated nitrile rubber (HNBR), and chloroprene rubber (CR) and ethylene-propylene-diene terpolymer (EPDM) are also suitably used. A particularly preferred rubber component for applications where a high load acts is a rubber with high heat aging resistance, particularly hydrogenated nitrile rubber (HNBR) which may be carboxylated (hereinafter, may be simply referred to as hydrogenated nitrile rubber, including carboxylated hydrogenated nitrile rubber). The proportion of the above-mentioned preferred rubber component in the rubber component is preferably 50% by mass or more (for example, about 80 to 100% by mass), and particularly preferably 100% by mass. The hydrogenated nitrile rubber which may be carboxylated may be a partially hydrogenated nitrile rubber or a fully hydrogenated nitrile rubber. The hydrogenation rate of the hydrogenated nitrile rubber which may be carboxylated may be selected from a range of about 50 to 100%, and may be 70 to 100%.

[0074] In this application, HNBR means a rubber having improved heat resistance by chemically hydrogenating the unsaturated bonds (carbon-carbon double bonds) of conventional nitrile rubber in order to prevent deterioration of rubber elasticity caused by recombination reaction of sulfur during heat aging while maintaining the oil resistance, which is an advantage of conventional nitrile rubber.

[0075] The iodine value (unit: mg / 100 mg) of HNBR is, for example, 5 to 60 (eg, 7 to 50), preferably 8 to 40 (eg, 8 to 35), and more preferably 10 to 30.

[0076] In this application, the iodine value is an index representing the amount of unsaturated bonds, and the higher the iodine value, the greater the amount of unsaturated bonds contained in the polymer molecular chain. The iodine value is determined by adding excess iodine to a measurement sample, allowing it to react completely (reacting iodine with unsaturated bonds), and quantifying the amount of remaining iodine by oxidation-reduction titration. When the iodine value of HNBR is low, the crosslinking reaction between HNBR is insufficient, and the rigidity of the crosslinked rubber is reduced, so there is a risk of the deformation resistance decreasing during belt running. On the other hand, when the iodine value of HNBR is high, the amount of unsaturated bonds becomes excessively large, and the thermal and oxidative deterioration of the crosslinked rubber progresses, and there is a risk of the belt life being shortened.

[0077] The rubber component preferably contains at least hydrogenated nitrile rubber which may be carboxylated. The proportion of such hydrogenated nitrile rubber in the rubber component may be 80 to 100% by mass, preferably 90 to 100% by mass, and more preferably 100% by mass.

[0078] The rubber component preferably contains a composite polymer containing hydrogenated nitrile rubber and an unsaturated carboxylate metal salt (hereinafter referred to as "HNBR / unsaturated carboxylate metal salt composite polymer"). This composite polymer may be a polymer alloy. In this application, the composite polymer contained in the first rubber component is referred to as the first composite polymer, and the composite polymer contained in the second rubber component is referred to as the second composite polymer. This polymer can increase the elastic modulus and hardness of the tooth portion, and can suppress deformation of the rubber and suppress the growth of cracks.

[0079] The unsaturated carboxylic acid metal salt may be a compound in which an unsaturated carboxylic acid having one or more carboxyl groups is ionically bonded to a metal.

[0080] Examples of the unsaturated carboxylic acid of the unsaturated carboxylic acid metal salt include monocarboxylic acids such as (meth)acrylic acid and crotonic acid, dicarboxylic acids such as maleic acid, fumaric acid and itaconic acid, and monoalkyl esters of these dicarboxylic acids. These unsaturated carboxylic acids can be used alone or in combination. A preferred unsaturated carboxylic acid is (meth)acrylic acid.

[0081] Examples of the metal of the unsaturated carboxylic acid metal salt include polyvalent metals, such as elements of Group 2 of the periodic table (magnesium, calcium, etc.), elements of Group 4 of the periodic table (titanium, zirconium, etc.), elements of Groups 8 to 14 of the periodic table (for example, iron, cobalt, nickel, copper, zinc, aluminum, tin, lead, etc.). These metals can be used alone or in combination of two or more. Preferred metals are elements of Group 2 of the periodic table (magnesium, etc.), elements of Group 12 of the periodic table (zinc, etc.), etc.

[0082] Preferable examples of the unsaturated carboxylic acid metal salt include zinc (meth)acrylate, magnesium (meth)acrylate, etc. The unsaturated carboxylic acid metal salt can be used alone or in combination of two or more kinds.

[0083] The HNBR / unsaturated carboxylic acid metal salt composite polymer may be a commercially available product, such as a product in which zinc methacrylate is highly finely dispersed in HNBR as an unsaturated carboxylic acid metal salt (for example, Zeoforte (ZSC) manufactured by Zeon Corporation).

[0084] The HNBR / unsaturated carboxylate metal salt composite polymer may be a mixture of a composite polymer in which an unsaturated carboxylate metal salt is finely dispersed in HNBR, and hydrogenated nitrile rubber (HNBR) that does not contain an unsaturated carboxylate metal salt. In other words, in the HNBR / unsaturated carboxylate metal salt composite polymer, the mass ratio of the hydrogenated nitrile rubber to the unsaturated carboxylate metal salt may be adjusted by mixing a commercially available HNBR containing an unsaturated carboxylate metal salt with a commercially available hydrogenated nitrile rubber. The elastic modulus and hardness may be adjusted by changing the mixing ratio of the two.

[0085] In the HNBR / unsaturated carboxylic acid metal salt composite polymer, the mass ratio of the hydrogenated nitrile rubber to the unsaturated carboxylic acid metal salt can be selected from the range of about 100 / 70 to 100 / 180, preferably 100 / 80 to 100 / 175, and more preferably 100 / 90 to 100 / 175. In the first rubber layer, the mass ratio is 100 / 90 to 100 / 170, preferably 100 / 95 to 100 / 150, and more preferably 100 / 100 to 100 / 120, and in the second rubber layer, the mass ratio is 100 / 70 to 100 / 110, preferably 100 / 75 to 100 / 100, and more preferably 100 / 80 to 100 / 90. If the proportion of the unsaturated carboxylic acid metal salt is too low, the elastic modulus and hardness of the crosslinked rubber composition (or the teeth) may decrease, whereas if the proportion is too high, the processability and flexibility of the belt may decrease.

[0086] The proportion of the HNBR / unsaturated carboxylic acid metal salt composite polymer in the rubber component may be 10% by mass or more, preferably 30% by mass or more, further preferably 50% by mass or more, more preferably 80% by mass or more, most preferably 90% by mass or more, and may be 100% by mass. In particular, the proportion of the HNBR / unsaturated carboxylic acid metal salt composite polymer in the first rubber layer is preferably 80% by mass or more (particularly 100% by mass) in the rubber component (first rubber component), and in the second rubber layer is preferably 30% by mass or more (particularly 100% by mass) in the rubber component (second rubber component). These proportions may be the proportions in the product "Zeoforte (ZSC)".

[0087] The other rubber component to be combined with the HNBR / unsaturated carboxylic acid metal salt composite polymer is preferably at least one selected from the group consisting of EPDM and CR. The proportion of the other rubber component in the rubber component is, for example, 70 mass% or less, preferably 50 mass% or less, more preferably 30 mass% or less, and most preferably 10 mass% or less.

[0088] In order to ensure adhesion between the layers, the first rubber layer and the second rubber layer preferably contain rubber components of the same series or type, more preferably the same type of rubber component, and even more preferably the same rubber component.

[0089] (B) Short Fiber As described above, the first crosslinked rubber composition contains the first short fibers as an essential component, but the second crosslinked rubber composition forming the second rubber layer may also contain the second short fibers.

[0090] Examples of the short fibers (first short fibers and second short fibers) include polyolefin fibers (polyethylene fibers, polypropylene fibers, etc.), polyamide fibers [aliphatic polyamide fibers (nylon fibers) such as polyamide 6 fibers, polyamide 66 fibers, and polyamide 46 fibers, aramid fibers, etc.], polyester fibers [polyalkylene arylate fibers (e.g., polyethylene terephthalate (PET) fibers, polytrimethylene terephthalate (PTT) fibers, polybutylene terephthalate (PBT) fibers, polyethylene naphthalate (PEN) fibers, etc. C fibers, etc. 2-4 Alkylene C 8-14Examples of the short fibers include synthetic fibers such as vinylon fibers, polyvinyl alcohol fibers, and polyparaphenylene benzobisoxazole (PBO) fibers; natural fibers such as cotton, hemp, and wool, regenerated cellulose fibers such as rayon, and cellulose ester fibers; and inorganic fibers such as carbon fibers and glass fibers. These short fibers can be used alone or in combination of two or more. In particular, fibers with a high modulus such as polyamide fibers, PBO fibers, glass fibers, and carbon fibers can be preferably used, and polyamide fibers such as aliphatic polyamide fibers (nylon fibers) and aramid fibers, and PBO fibers are more preferable, and aliphatic polyamide fibers are most preferable as the first short fibers, and aramid fibers are most preferable as the second short fibers.

[0091] The average fiber diameter of the short fibers is, for example, 1 to 100 μm (e.g., 3 to 70 μm), preferably 5 to 50 μm (e.g., 7 to 30 μm), and more preferably 10 to 25 μm (particularly 12 to 20 μm). The average fiber length of the short fibers is, for example, 0.3 to 10 mm (e.g., 0.5 to 7 mm), and preferably 1 to 5 mm (particularly 2 to 4 mm). If the average fiber diameter of the short fibers is too small or the average fiber length is too long, the short fibers may not be uniformly dispersed or may be difficult to orient in a predetermined direction, whereas if the average fiber diameter is too large or the average fiber length is too short, the mechanical properties of each rubber layer may be reduced.

[0092] It is also preferable to subject the short fibers to a conventional adhesive treatment (or surface treatment) to adhere an adhesive component to at least a portion of the surface of the short fibers. Such an adhesive treatment improves the adhesion between the short fibers and the rubber component, and can suppress the occurrence of microcracks originating from the interface between the short fibers and the rubber component. Examples of the adhesive treatment include treatment with an adhesive component such as an epoxy compound (or epoxy resin), polyisocyanate, a silane coupling agent, or resorcin-formaldehyde-latex (RFL).

[0093] In the first crosslinked rubber composition, the proportion of the first short fibers may be 5 to 60 parts by mass (particularly 10 to 60 parts by mass) relative to 100 parts by mass of the first rubber component, as described above, and is preferably 8 to 55 parts by mass (e.g., 10 to 50 parts by mass), further preferably 15 to 45 parts by mass, further preferably 20 to 40 parts by mass, and most preferably 25 to 35 parts by mass. If the proportion of the first short fibers is too low, the tooth chipping resistance decreases, and conversely, if it is too high, the effect of blending the short fibers decreases and the mechanical properties of the first rubber layer decrease.

[0094] The second crosslinked rubber composition does not necessarily need to contain the second short fibers, but it is preferable that the second crosslinked rubber composition contains the second short fibers in order to improve the mechanical properties of the second rubber layer.

[0095] The ratio of the second short fibers to the second rubber component is preferably smaller than the ratio of the first short fibers to the first rubber component in order to improve tooth chipping resistance. The ratio of the second short fibers may be 10 parts by mass or less (0 to 10 parts by mass), particularly 5 parts by mass or less (for example, 3 parts by mass or less) relative to 100 parts by mass of the second rubber component, and is preferably 0.1 to 5 parts by mass (for example, 0.3 to 4 parts by mass), more preferably 0.5 to 3.5 parts by mass, more preferably 1 to 3 parts by mass, and most preferably 1.5 to 2.5 parts by mass. If the ratio of the second short fibers is too high, the elastic modulus and hardness of the second crosslinked rubber composition can be increased, but microcracks are likely to occur at the interface between the second rubber component and the second short fibers, which may reduce tooth chipping resistance.

[0096] When the second crosslinked rubber composition contains the second short fibers, the orientation direction of the second short fibers is not particularly limited, but it is preferable to arrange them in the belt longitudinal direction like the first short fibers. Furthermore, when the second crosslinked rubber composition contains the second short fibers, it is preferable to arrange the second short fibers so that the second short fibers are oriented along the contour of the tooth portion on the side closer to the tooth cloth, and the second short fibers are oriented approximately parallel to the core wire as they approach the core wire.

[0097] (C) Filler compounding agents The crosslinked rubber composition (the first crosslinked rubber composition and the second crosslinked rubber composition) may further contain a filler. Examples of the filler (the first filler and the second filler) include a reinforcing inorganic filler and a non-reinforcing filler.

[0098] Examples of the reinforcing inorganic filler (the first reinforcing inorganic filler and the second reinforcing inorganic filler) include carbon black and silica. These reinforcing inorganic fillers can be used alone or in combination of two or more. The reinforcing inorganic filler may be in a powder form.

[0099] The average particle size (average primary particle size) of carbon black is, for example, 5 to 200 nm, preferably 10 to 150 nm, more preferably 20 to 100 nm, and more preferably 30 to 80 nm. The iodine adsorption amount of carbon black is, for example, 5 to 200 mg / g, preferably 10 to 150 mg / g, more preferably 15 to 100 mg / g, and more preferably 20 to 80 mg / g.

[0100] Silica includes dry silica, wet silica, surface-treated silica, etc. Silica can also be classified into dry white carbon, wet white carbon, colloidal silica, precipitated silica, etc., depending on the manufacturing method. These silicas can be used alone or in combination of two or more. Among these silicas, silica having a surface silanol group (anhydrous silicic acid, hydrous silicic acid) is preferred, and hydrous silicic acid having many surface silanol groups has a strong chemical bond with the rubber component.

[0101] The average particle size (average primary particle size) of the silica is, for example, 1 to 500 nm, preferably 3 to 300 nm, further preferably 5 to 100 nm, and further preferably 10 to 50 nm.

[0102] The nitrogen adsorption specific surface area of ​​silica by the BET method is, for example, 50 to 400 m 2 / g, preferably 100 to 300m 2 / g, more preferably 150 to 200m 2 / g.

[0103] In the present application, the average particle size of the reinforcing inorganic filler can be calculated as the arithmetic average particle size of an appropriate number of samples (for example, 50 samples) by image analysis of electron microscope photographs, including scanning electron microscope photographs.

[0104] The proportion of the reinforcing inorganic filler may be 10 parts by mass or less, preferably 5 parts by mass or less, more preferably 1 part by mass or less, and more preferably 0 parts by mass, based on 100 parts by mass of the rubber component. When a reinforcing inorganic filler is used as necessary, the proportion of the reinforcing inorganic filler may be, for example, 0.1 to 8 parts by mass, preferably 0.5 to 5 parts by mass, and more preferably 1 to 3 parts by mass, based on 100 parts by mass of the rubber component. If the proportion of the reinforcing inorganic filler is too high, heat generation of the rubber composition increases and heat resistance decreases, which may cause cracks and chipped teeth due to thermal deterioration.

[0105] Examples of non-reinforcing fillers (first non-reinforcing filler and second non-reinforcing filler) include polyvalent metal carbonates (calcium carbonate, magnesium carbonate, etc.), polyvalent metal hydroxides (aluminum hydroxide, etc.), polyvalent metal sulfates (barium sulfate, etc.), silicates (natural or synthetic silicates in which part of silicon is replaced with polyvalent metal atoms, such as aluminum silicate, magnesium silicate, and aluminum magnesium silicate; minerals containing silicate as the main component, such as clay containing aluminum silicate, talc containing magnesium silicate, and silicate minerals such as mica), lithopone, silica sand, etc. These non-reinforcing fillers can be used alone or in combination of two or more.

[0106] A preferred non-reinforcing filler is at least one selected from calcium carbonate, magnesium carbonate, aluminum hydroxide, barium sulfate, and silicates [silicates such as aluminum silicate, magnesium silicate, and aluminum magnesium silicate; silicate minerals (talc, clay, mica, etc.)]. Furthermore, the non-reinforcing filler is preferably at least one selected from calcium carbonate, magnesium silicate or talc containing magnesium silicate, aluminum silicate or clay containing aluminum silicate, and particularly preferably contains calcium carbonate, since it has a large effect of improving the processability of the belt and the dispersibility of the compounding agent, and is less likely to cause poor dispersion of the compounding agent. As the non-reinforcing filler, a powdered filler commercially available as a rubber filler can be used.

[0107] The average particle size (average primary particle size) of the non-reinforcing filler can be selected from the range of, for example, 0.01 to 25 μm (for example, 0.2 to 20 μm), preferably 0.5 to 17 μm (for example, 1 to 15 μm). The average particle size (average primary particle size) of the non-reinforcing filler may be, for example, 0.01 to 3 μm (for example, 0.02 to 2 μm), preferably 0.05 to 1.5 μm (particularly 0.1 to 1 μm), or may be relatively large. The average particle size (average primary particle size) of the non-reinforcing filler may be, for example, 0.2 to 5 μm (for example, 0.3 to 3 μm), preferably 0.5 to 2.5 μm (particularly 1 to 2 μm). Depending on the type of non-reinforcing filler, for example, magnesium silicate or its mineral, the non-reinforcing filler may be crushed or crushed during the kneading process with the rubber component or the like. The average particle size of such a crushable or crushable non-reinforcing filler may be the average particle size before kneading with the rubber component, etc. The non-reinforcing filler may usually have an average particle size in the above range (for example, 0.1 to 10 μm, preferably 0.5 to 5 μm, and more preferably 1 to 3 μm) in each crosslinked rubber composition.

[0108] In the present application, the average particle size of the non-reinforcing filler can be measured as the volume average particle size using a laser diffraction particle size distribution analyzer. The average particle size of the nanometer-sized filler can be calculated as the arithmetic average particle size of an appropriate number of samples (e.g., 50 samples) by image analysis of electron microscope photographs, including scanning electron microscope photographs.

[0109] The proportion of the non-reinforcing filler is, for example, 70 parts by mass or less, preferably 40 parts by mass or less, and more preferably 30 parts by mass or less, based on 100 parts by mass of the rubber component. When a non-reinforcing filler is used as necessary, the proportion of the non-reinforcing filler may be, for example, 3 to 70 parts by mass, preferably 5 to 40 parts by mass, and more preferably 10 to 30 parts by mass, based on 100 parts by mass of the rubber component. If the proportion of the non-reinforcing filler is too high, there is a risk that the dispersibility of the compounding ingredients will be poor.

[0110] The ratio of the filler compounding agent is, for example, 3 to 70 parts by mass, preferably 5 to 50 parts by mass, further preferably 10 to 40 parts by mass, and further preferably 20 to 30 parts by mass, based on 100 parts by mass of the rubber component.

[0111] (D) Crosslinking compounding agents The rubber composition is compounded with a crosslinking agent (vulcanizing agent) for crosslinking the rubber component, and, if necessary, with a co-crosslinking agent, a crosslinking assistant (vulcanization assistant), a crosslinking accelerator (vulcanization accelerator), a crosslinking retarder (vulcanization retarder), etc. Among these, the crosslinking compounding agents (first crosslinking compounding agent and second crosslinking compounding agent) preferably contain at least a crosslinking agent and a co-crosslinking agent (crosslinking assistant), and a combination of a crosslinking agent and a co-crosslinking agent is particularly preferred.

[0112] As the crosslinking agent (first crosslinking agent and second crosslinking agent), a conventional component can be used depending on the type of rubber component, and examples thereof include organic peroxides, sulfur-based crosslinking agents, and metal oxides.

[0113] Examples of organic peroxides (first organic peroxide and second organic peroxide) include di-t-butyl peroxide, dicumyl peroxide, t-butylcumyl peroxide, 1,1-t-butylperoxy-3,3,5-trimethylcyclohexane, 1,3-bis(t-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, 1,3-bis(t-butylperoxy-di-isopropyl)benzene, 2,5-di-methyl-2,5-di(benzoylperoxy)hexane, t-butylperoxybenzoate, and t-butylperoxy-2-ethyl-hexyl carbonate. These organic peroxides can be used alone or in combination.

[0114] Examples of sulfur-based crosslinking agents include powdered sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, sulfur chlorides (sulfur monochloride, sulfur dichloride, etc.), etc. These sulfur-based crosslinking agents can be used alone or in combination of two or more.

[0115] Examples of metal oxides include magnesium oxide, zinc oxide, lead oxide, etc. These metal oxides may be used alone or in combination.

[0116] The crosslinking agent can be appropriately selected depending on the type of rubber component, and is preferably an organic peroxide or a metal oxide, more preferably an organic peroxide, or may be a combination of an organic peroxide and a metal oxide.

[0117] The proportion of the crosslinking agent is, for example, 1 to 20 parts by mass, preferably 3 to 15 parts by mass, and more preferably 5 to 10 parts by mass, based on 100 parts by mass of the rubber component. If the proportion of the crosslinking agent is too low, the elastic modulus and hardness of the rubber composition decrease, whereas if the proportion is too high, the flexibility of the belt decreases.

[0118] The ratio of the organic peroxide can be selected from the range of about 0.5 to 20 parts by mass (e.g., 1 to 10 parts by mass) relative to 100 parts by mass of the rubber component, and is usually 1 to 5 parts by mass (e.g., 1.2 to 4.5 parts by mass), preferably 1.5 to 4 parts by mass, and more preferably 2 to 3 parts by mass. In the first rubber layer, the ratio of the first organic peroxide is, for example, 1 to 20 parts by mass, preferably 1.5 to 10 parts by mass, and more preferably 1.5 to 4 parts by mass, relative to 100 parts by mass of the first rubber component. In the second rubber layer, the ratio of the second organic peroxide is, for example, 0.5 to 5 parts by mass, preferably 0.8 to 4 parts by mass, and more preferably 1 to 3 parts by mass, relative to 100 parts by mass of the second rubber component.

[0119] The proportion of the metal oxide is, for example, 0.1 to 30 parts by mass, preferably 0.5 to 20 parts by mass, further preferably 1 to 15 parts by mass, further preferably 2 to 10 parts by mass, and most preferably 3 to 7 parts by mass, based on 100 parts by mass of the rubber component.

[0120] Examples of the co-crosslinking agent (crosslinking aid or co-vulcanizing agent) include known crosslinking aids, such as polyfunctional (iso)cyanurates [e.g., triallyl isocyanurate (TAIC), triallyl cyanurate (TAC), etc.], polydiene (e.g., 1,2-polybutadiene, etc.), metal salts of unsaturated carboxylic acids [e.g., (meth)acrylic acid polyvalent metal salts such as zinc (meth)acrylate and magnesium (meth)acrylate], oximes (e.g., quinone dioxime, etc.), guanidines (e.g., diphenyl guanidine, etc.), polyfunctional (meth)acrylates [e.g., alkanediol di(meth)acrylate such as ethylene glycol di(meth)acrylate and butanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetraacetate, etc., alkane polyol poly(meth)acrylates such as cyclohexyl (meth)acrylate, bismaleimides (aliphatic bismaleimides such as alkylene bismaleimides such as N,N'-1,2-ethylene dimaleimide, N,N'-hexamethylene bismaleimide, 1,6'-bismaleimide-(2,2,4-trimethyl)cyclohexane; arene bismaleimides or aromatic bismaleimides such as N,N'-m-phenylene dimaleimide, 4-methyl-1,3-phenylene dimaleimide, 4,4'-diphenylmethane dimaleimide, 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane, 4,4'-diphenylether dimaleimide, 4,4'-diphenylsulfone dimaleimide, 1,3-bis(3-maleimidophenoxy)benzene, etc.). These co-crosslinking agents can be used alone or in combination of two or more. Among these co-crosslinking agents, polyfunctional (iso)cyanurates, polyfunctional (meth)acrylates, and bismaleimides (arene bismaleimides such as N,N'-m-phenylenedimaleimide or aromatic bismaleimides) are preferred, and bismaleimides are particularly preferred. The addition of a co-crosslinking agent (e.g., bismaleimides) can increase the degree of crosslinking and improve the elastic modulus.

[0121] The ratio of the co-crosslinking agent (crosslinking assistant) such as bismaleimides is, for example, 0.2 to 40 parts by mass, preferably 0.5 to 30 parts by mass, more preferably 0.8 to 20 parts by mass, and more preferably 1 to 15 parts by mass, based on 100 parts by mass of the rubber component, calculated as solid content. In the first rubber layer, the ratio of the co-crosslinking agent (first co-crosslinking agent) is, for example, 1 to 40 parts by mass, preferably 2 to 30 parts by mass (for example, 5 to 20 parts by mass), more preferably 2.5 to 18 parts by mass (for example, 8 to 15 parts by mass), more preferably 3 to 14 parts by mass (for example, 4 to 12 parts by mass), and most preferably 5 to 11 parts by mass (for example, 5 to 7 parts by mass), based on 100 parts by mass of the first rubber component. In the second rubber layer, the ratio of the co-crosslinking agent (second co-crosslinking agent) can be selected from the range of about 0.2 to 25 parts by mass relative to 100 parts by mass of the second rubber component, for example, 0.3 to 20 parts by mass (e.g., 0.5 to 10 parts by mass), preferably 0.5 to 7 parts by mass (e.g., 0.5 to 6 parts by mass), further preferably 0.8 to 5 parts by mass, more preferably 0.8 to 3 parts by mass, and most preferably 0.8 to 2 parts by mass. In particular, when the ratio of the first co-crosslinking agent in the first rubber component is adjusted to 3 parts by mass or more (particularly 5 parts by mass or more), the tooth chipping resistance of the toothed belt can be highly improved by the effect of combination with the first short fibers oriented in a predetermined direction.

[0122] The ratio of the crosslinking compounding agent is, for example, 0.2 to 50 parts by mass, preferably 0.5 to 40 parts by mass, more preferably 1 to 30 parts by mass, and more preferably 2 to 20 parts by mass, based on 100 parts by mass of the rubber component, calculated as solid content. In the first rubber layer, the ratio of the crosslinking compounding agent (first crosslinking compounding agent) is, for example, 1 to 40 parts by mass, preferably 5 to 20 parts by mass, and more preferably 10 to 15 parts by mass, based on 100 parts by mass of the first rubber component. In the second rubber layer, the ratio of the crosslinking compounding agent (second crosslinking compounding agent) is, for example, 0.3 to 25 parts by mass, preferably 0.5 to 10 parts by mass, and more preferably 1 to 8 parts by mass, based on 100 parts by mass of the second rubber component.

[0123] (E) Other compounding agents The crosslinked rubber composition may further contain customary additives used in rubber compositions for toothed belts. Examples of commonly used additives include metal oxides (calcium oxide, barium oxide, iron oxide, copper oxide, titanium oxide, aluminum oxide, etc.), softeners (oils such as paraffin oil and naphthenic oil), processing agents or processing aids (stearic acid or metal salts thereof, wax, paraffin, fatty acid amides, etc.), plasticizers [aliphatic carboxylic acid ester plasticizers (adipate ester plasticizers, sebacate ester plasticizers, etc.), aromatic carboxylic acid ester plasticizers (phthalate ester plasticizers, trimellitate ester plasticizers, etc.), oxycarboxylic acid ester plasticizers, phosphate ester plasticizers, ether plasticizers, ether ester plasticizers, etc.], antiaging agents (antioxidants, heat antiaging agents, flex crack inhibitors, ozone degradation inhibitors, etc.), colorants, tackifiers, plasticizers, coupling agents (silane coupling agents, etc.), stabilizers (ultraviolet light absorbers, heat stabilizers, etc.), flame retardants, antistatic agents, etc. Furthermore, the crosslinked rubber composition may contain an adhesion improver (resorcinol-formaldehyde co-condensation product, amino resin, etc.) if necessary. These additives may be used alone or in combination of two or more kinds.

[0124] In particular, the proportion of the processing agent or processing aid can be selected from the range of, for example, about 0.1 to 10 parts by mass relative to 100 parts by mass of the rubber component, and may be 0.3 to 3 parts by mass (particularly 0.5 to 1.5 parts by mass) in the first rubber layer and 0.1 to 2 parts by mass (particularly 0.3 to 1 part by mass) in the second rubber layer.

[0125] The proportion of the antioxidant relative to 100 parts by mass of the rubber component is, for example, 0.1 to 10 parts by mass, preferably 0.5 to 5 parts by mass, and more preferably 1 to 3 parts by mass.

[0126] (Preferable compounding mode of the first rubber layer and the second rubber layer) The elastic modulus of the first rubber layer and the second rubber layer can be adjusted by changing the quantitative ratio of a predetermined component that affects the elastic modulus of the rubber layer. For example, the content of at least one component selected from short fibers, filler compounding agents, crosslinking compounding agents [crosslinking agents, co-crosslinking agents (such as bismaleimides)] may be increased in the first rubber layer compared to the second rubber layer. In particular, in the toothed belt of the present invention, since the first rubber layer contains a predetermined amount of first short fibers as an essential component, the elastic modulus can be easily adjusted by adjusting the ratio of the second short fibers in the second rubber layer. Furthermore, by making the ratio of the second short fibers in the second rubber layer smaller than the ratio of the first short fibers in the first rubber layer, the occurrence of microcracks in the second rubber layer can also be suppressed, thereby improving tooth chipping resistance. Furthermore, by adjusting the content of the co-crosslinking agent (particularly bismaleimides) in addition to the proportion of short fibers, the elastic modulus (tensile modulus) of the first rubber layer and the second rubber layer can be adjusted in a well-balanced manner, making it possible to achieve both the rigidity (resistance to deformation) and flexibility (suppleness) of the tooth portion, which are in a trade-off relationship, and also highly improving tooth chipping resistance.

[0127] Furthermore, in the toothed belt of the present invention, in order to have a high elastic modulus to obtain rigidity in the teeth portion capable of withstanding use under conditions of higher load, and to achieve a balance between the rigidity (resistance to deformation) and flexibility (suppleness) of the teeth portion, which are in a trade-off relationship, the following composition is a preferred embodiment.

[0128] In a preferred embodiment, in the first rubber layer, the first rubber component contains 80% by mass or more of HNBR containing an unsaturated carboxylic acid metal salt, and, relative to 100 parts by mass of the first rubber component, the ratio of the first short fiber is 5 to 60 parts by mass, the ratio of the first reinforcing inorganic filler is 10 parts by mass or less, the ratio of the bismaleimide as a first co-crosslinking agent is 1 to 40 parts by mass, and the ratio of the organic peroxide as the first crosslinking agent is 1 to 20 parts by mass; and, in the second rubber layer, the second rubber component contains 30% by mass or more of HNBR containing an unsaturated carboxylic acid metal salt, and, relative to 100 parts by mass of the second rubber component, the ratio of the second short fiber is 5 parts by mass or less, the ratio of the second reinforcing inorganic filler is 10 parts by mass or less, the ratio of the bismaleimide as a second co-crosslinking agent is 0.2 to 25 parts by mass, and the ratio of the organic peroxide as the second crosslinking agent is 0.5 to 5 parts by mass.

[0129] (Tooth cloth) When the tooth portion includes a tooth cloth, the tooth cloth constituting the inner peripheral surface of the belt (the surface of the tooth portion and the tooth bottom portion) may be formed of a fabric such as a woven fabric, a knitted fabric, or a nonwoven fabric. Conventionally, it is often a woven fabric (canvas), and is composed of a fabric woven with warp threads extending in the width direction of the belt and weft threads extending in the circumferential direction of the belt. The weave structure of the woven fabric is not particularly limited as long as the warp threads and weft threads are regularly crossed in the vertical and horizontal directions, and may be any of plain weave, twill weave (or twill weave), satin weave (satin weave), etc., or a combination of these weaves. Preferred woven fabrics have twill and satin weave structures.

[0130] Examples of fibers forming the weft and warp of the tooth cloth include polyphenylene ether fibers, polyether ether ketone fibers, polyether sulfone fibers, and polyurethane fibers, in addition to the same fibers as the short fibers. These fibers can be used alone or in combination of two or more. Among these fibers, organic fibers are widely used, and preferred are cellulose fibers such as cotton and rayon, polyester fibers (PET fibers, etc.), polyamide fibers (aliphatic polyamide fibers such as polyamide 66 fibers, aramid fibers, etc.), PBO fibers, and fluororesin fibers (polytetrafluoroethylene (PTFE) fibers, etc.). Also preferred are composite yarns of these fibers and elastic elastic yarns (for example, polyurethane elastic yarns such as spandex formed of polyurethane, and processed yarns that have been stretched (for example, woolly processing, shrink processing, etc.)).

[0131] The form of the warp and weft yarns is not particularly limited, and may be a monofilament yarn, which is a single long fiber, a multifilament yarn in which filaments (long fibers) are aligned or twisted together, a spun yarn (spun yarn) in which short fibers are twisted together, or the like. The multifilament yarn or the spun yarn may be a mixed twisted yarn or a mixed spun yarn using a plurality of types of fibers. The weft yarn preferably contains an elastic yarn having the above-mentioned stretchability, and in many cases, the warp yarn does not usually contain an elastic yarn in terms of weaving. In order to ensure the stretchability of the tooth cloth in the circumferential direction of the belt, the weft yarn containing the elastic yarn extends in the circumferential direction of the belt, and the warp yarn extends in the width direction of the belt.

[0132] The average diameter of the fibers (or threads) is, for example, 1 to 100 μm (e.g., 3 to 50 μm), preferably 5 to 30 μm, and more preferably 7 to 25 μm. Regarding the average fiber diameter (thickness) of the threads (twisted yarns), the weft may be, for example, about 100 to 1000 dtex (particularly, 300 to 700 dtex), and the warp may be, for example, about 50 to 500 dtex (particularly, 100 to 300 dtex). The density of the weft (pieces / cm) may be, for example, about 5 to 50 (particularly, 10 to 30), and the density of the warp (pieces / cm) may be, for example, about 10 to 300 (particularly, 20 to 100).

[0133] The woven fabric may have a multi-weave structure (e.g., double-weave structure), and in a weave structure having warp threads and weft threads, at least some of the weft threads may be formed of a fiber with a low friction coefficient (or a low-friction fiber) such as a fluororesin-containing fiber (e.g., a composite thread containing a fiber formed of a fluororesin such as PTFE). For example, the warp threads may be formed of polyamide fibers such as nylon 66, polyester fibers, etc., and the weft threads may be formed of a single fiber formed of the fluororesin; a composite thread of a fiber formed of the fluororesin and a second fiber such as a polyamide fiber or a polyurethane fiber (elastic thread); a composite thread of this composite thread and a second composite thread formed of the plurality of second fibers; or the like.

[0134] In this embodiment, it is preferable to use a fluorine-based fiber (e.g., PTFE fiber) having a low friction coefficient as the weft yarn located (exposed) on the front side of the tooth cloth (the side that meshes with the toothed pulley) in order to reduce friction between the tooth cloth and the toothed pulley. On the other hand, by using a fiber other than the fluorine-based fiber for the weft yarn located on the back side of the tooth cloth (the side that adheres to the first rubber layer), it is possible to increase the adhesive strength between the tooth cloth and the rubber that constitutes the teeth. With the tooth cloth of this embodiment, friction at the meshing between the tooth cloth and the toothed pulley can be reduced, and noise can be suppressed.

[0135] In addition, when using fluorine-based fibers, it is preferable that low-melting-point fibers having a melting point that melts at the crosslinking (vulcanization) temperature of the tooth part and back part based on rubber are arranged around the fluorine-based fibers. Specifically, the form of the composite yarn containing fluorine-based fibers includes a form in which fluorine-based fibers and low-melting-point fibers are mixed and twisted, and a form in which fluorine-based fibers are covered with low-melting-point fibers. The crosslinking (vulcanization) conditions of the tooth part and back part are not particularly limited, and generally, the crosslinking (vulcanization) temperature is 100 to 200°C, and the crosslinking (vulcanization) time is about 1 minute to 5 hours.

[0136] In an embodiment in which low melting point fibers are arranged around the fluorine-based fibers, the low melting point fibers melt during crosslinking (vulcanization) of the teeth and back, flow into the spaces between the fibers that make up the tooth cloth, and then crystallize by cooling below the melting point. This prevents the fluorine-based fibers from being cut or scattered by the impact or wear that occurs on the surface of the tooth cloth when the tooth cloth is engaged with or disengaged from the toothed pulley. When the weft yarn of the above embodiment is used as the tooth cloth of a toothed belt, the teeth and back are protected for a longer period of time due to the above action, preventing the belt from chipping, and enabling a longer life during high-load driving.

[0137] The tooth cloth (tooth cloth in the toothed belt) has an average thickness of, for example, 0.1 to 2 mm, preferably 0.2 to 1.5 mm. The tooth cloth as a raw material (tooth cloth before molding) has an average thickness of, for example, 0.5 to 3 mm, preferably 0.75 to 2.5 mm.

[0138] In order to enhance adhesion to the first rubber layer, the fabric forming the tooth cloth may be subjected to an adhesive treatment. Examples of adhesive treatment include a method of immersing the fabric in an RFL treatment liquid and then drying by heating; a method of treating with an epoxy compound or an isocyanate compound; a method of dissolving a rubber composition in an organic solvent to prepare a rubber paste, immersing the fabric in the rubber paste and then drying by heating; and a method combining these treatment methods. These methods may be performed alone or in combination, and the order of treatment and the number of treatments are not limited. For example, the fabric may be immersed in an RFL treatment liquid, and then further immersed in rubber paste and then dried by heating.

[0139] Furthermore, in order to enhance the adhesion between the tooth cloth and the first rubber layer, an uncrosslinked rubber sheet formed by rolling a rubber composition may be laminated on the back surface (adhesive side with the first rubber layer) of the cloth forming the tooth cloth. This rubber composition (third crosslinked rubber composition) can be appropriately selected from the crosslinked rubber compositions exemplified as the crosslinked rubber compositions forming the first rubber layer and the second rubber layer, and may be a conventional adhesive rubber composition. The uncrosslinked rubber sheet made of this rubber composition may form a third rubber layer (adhesive rubber layer) interposed between the tooth cloth and the first rubber layer in the toothed belt. The cloth subjected to the above-mentioned adhesive treatment is referred to as a tooth cloth precursor.

[0140] [Tooth bottom] When the tooth portion includes a tooth cloth, the tooth cloth constitutes the surface of the tooth portion and also constitutes the surface of the back portion on the tooth portion side (the surface of the tooth bottom portion).

[0141] When the tooth portion includes a tooth cloth, the first and second rubber layers may be interposed between the tooth cloth and the core wire in the back portion corresponding to the tooth bottom portion, but only the first rubber layer may be interposed, or the tooth cloth and the core wire may be in contact without the first and second rubber layers. Whether the first rubber layer is interposed in the back portion corresponding to the tooth bottom portion, or whether the first and second rubber layers are interposed, the thickness of the first rubber layer and the thickness of the first and second rubber layers are formed thinner than the tooth portion in either case.

[0142] When the tooth portion does not include a tooth cloth, the back portion corresponding to the tooth bottom portion may be formed of the first rubber layer and the second rubber layer, or may be formed of only the first rubber layer. In either case, the thickness of the first rubber layer, and the thickness of the first rubber layer and the second rubber layer in the back portion corresponding to the tooth bottom portion are formed thinner than the tooth portion.

[0143] [Back rubber layer] The back portion has the teeth and tooth bottoms formed on the inner peripheral surface, and has a back rubber layer that forms the outer peripheral surface of the belt on the outer peripheral surface side. Furthermore, the back rubber layer is formed of a crosslinked rubber composition (fourth crosslinked rubber composition). In the embodiment of Figs. 1 to 3, the other surface (back surface of the belt) on the side where the teeth are not formed is not covered with a fabric (woven fabric, knitted fabric, nonwoven fabric, etc.), but may be covered as necessary. This fabric can be selected from the fabrics exemplified as the tooth fabric, including the preferred embodiment.

[0144] (Fourth crosslinked rubber composition) The hardness of the fourth crosslinked rubber composition is preferably smaller than the hardness of the first crosslinked rubber composition and the second crosslinked rubber composition constituting the tooth portion, in order to reduce the bending rigidity of the belt and ensure flexibility (windability around a pulley) and bending fatigue resistance.

[0145] Specifically, the rubber hardness Hs of the fourth crosslinked rubber composition is, for example, 80 to 89 degrees in type A hardness. Also, it may be about 20 to 30 degrees in type D hardness. By adjusting the hardness of the back rubber layer within the above range, the bending rigidity of the back portion is reduced, and excellent resistance to bending fatigue is obtained. If the type A hardness of the fourth crosslinked rubber composition is too low, there is a risk of cracks occurring in the back portion due to collision with a foreign object, etc., and conversely, if it is too high, there is a risk of the bending fatigue resistance decreasing and cracks occurring in the back portion.

[0146] In the present application, the type A hardness refers to the hardness of the surface of the back rubber layer, and can be measured using a type A durometer in accordance with the spring type durometer hardness test specified in JIS K 6253 (2012).

[0147] The fourth cross-linked rubber composition is not particularly limited as long as it does not impair the adhesion between the back rubber layer and the tooth portion, and can be selected, for example, from the cross-linked rubber compositions exemplified as the cross-linked rubber compositions of the first rubber layer and the second rubber layer, and can be appropriately adjusted so that the rubber hardness is within the above-mentioned range.

[0148] In the fourth crosslinked rubber composition, the rubber component (fourth rubber component) preferably contains a rubber component of the same series or type as the second rubber layer (inner rubber layer), and more preferably the same type of rubber component, in order to improve adhesion between the back rubber layer and the tooth portion.

[0149] The fourth rubber component preferably contains an HNBR / unsaturated carboxylic acid metal salt composite polymer. The proportion of the HNBR / unsaturated carboxylic acid metal salt composite polymer in the fourth rubber component may be 5% by mass or more, for example, 5 to 50% by mass, preferably 10 to 30% by mass, and more preferably 15 to 25% by mass.

[0150] The filler compounding agent may be a reinforcing inorganic filler (fourth reinforcing inorganic filler), and a combination of carbon black and silica is preferable. The proportion of carbon black is, for example, 1 to 50 parts by mass, preferably 2 to 30 parts by mass, and more preferably 3 to 10 parts by mass, relative to 100 parts by mass of silica. The proportion of the fourth reinforcing inorganic filler is, for example, 10 to 100 parts by mass, preferably 20 to 80 parts by mass, and more preferably 30 to 50 parts by mass, relative to 100 parts by mass of the fourth rubber component.

[0151] The crosslinking agent (fourth crosslinking agent) may be a combination of an organic peroxide (fourth organic peroxide) and a metal oxide (fourth metal oxide). The proportion of the fourth organic peroxide is, for example, 0.5 to 5 parts by mass, preferably 0.8 to 4 parts by mass, and more preferably 1 to 3 parts by mass, relative to 100 parts by mass of the fourth rubber component. The proportion of the fourth metal oxide is, for example, 1 to 15 parts by mass, preferably 2 to 10 parts by mass, and more preferably 2 to 8 parts by mass, relative to 100 parts by mass of the fourth rubber component.

[0152] The co-crosslinking agent (fourth co-crosslinking agent) may be a bismaleimide. The proportion of the fourth co-crosslinking agent is, for example, 0.2 to 10 parts by mass, preferably 0.5 to 5 parts by mass, and more preferably 1 to 3 parts by mass, based on 100 parts by mass of the fourth rubber component.

[0153] The fourth crosslinked rubber composition may contain a plasticizer. The plasticizer may be selected from the plasticizers exemplified for the first rubber layer and the second rubber layer. The plasticizer may be used alone or in combination of two or more kinds. Among the plasticizers, ether ester plasticizers are preferred.

[0154] The proportion of the plasticizer relative to 100 parts by mass of the fourth rubber component is, for example, 1 to 50 parts by mass, preferably 2 to 30 parts by mass, further preferably 3 to 20 parts by mass, and further preferably 5 to 15 parts by mass.

[0155] The average thickness of the back rubber layer is, for example, 0.3 to 3 mm, preferably 0.5 to 2 mm. The average thickness of the back portion (average thickness of the back portion at the tooth bottom) is, for example, 1 to 5 mm, preferably 1.5 to 4 mm.

[0156] [Core] In the back portion, a core wire extending along the belt circumferential direction is embedded on the inner periphery side of the back rubber layer. This core wire acts as a tension member and can improve the running stability and strength of the toothed belt. Furthermore, in the back portion, the core wire, which is a twisted cord extending along the belt circumferential direction, is usually embedded in the belt width direction at a predetermined interval, and although multiple core wires parallel to the longitudinal direction may be arranged, from the viewpoint of productivity, it is usually embedded in a spiral shape. When arranged in a spiral shape, the angle of the core wire with respect to the belt longitudinal direction may be, for example, 5° or less, and from the viewpoint of belt running properties, the closer to 0° the more preferable.

[0157] More specifically, the core wires may be embedded at a predetermined interval (or pitch) (or at equal intervals) from one end to the other end in the belt width direction of the back part, as shown in Fig. 1. The interval (spinning pitch), which is the distance between the centers of adjacent core wires, may be larger than the diameter of the core wire, and is, for example, 0.5 to 3.5 mm, preferably 0.8 to 3 mm, and more preferably 0.9 to 2.8 mm, depending on the diameter of the core wire.

[0158] The core wire may be formed of a twisted cord made by twisting together a plurality of strands or multifilament yarns. Of these, a twisted cord made of strands is preferred, and one strand may be formed by bundling filaments (long fibers). There are no particular limitations on the thickness of the filaments forming the twisted cord, the number of filaments bundled together, the number of strands, and the twisting configuration.

[0159] The twisted cord forming the core wire may be a single-twist, double-twist, or Lang-twisted cord. As the twisting method of the twisted cord, single-twist and Lang-twist are preferred, and Lang-twist is particularly preferred. By using Lang-twist, in which the twisting direction of the first twist is the same as that of the top twist, the bending rigidity is lower than that of double-twist or single-twist, and excellent bending fatigue resistance is obtained.

[0160] In the present invention, by controlling the elastic modulus of the toothed belt described below by adjusting the elastic modulus, twist coefficient, core wire diameter D, core wire pitch P, and arrangement density of the core wire, it is possible to ensure jumping resistance, tension retention, and bending fatigue resistance even when the belt is narrowed in width for application to high-load transmission applications in rear-wheel drive of motorcycles.

[0161] In the present invention, regarding the elastic modulus of the core wire, by including a high elastic modulus fiber in the core wire, the elastic modulus (modulus) of the belt can be increased, and the jumping resistance in the above-mentioned applications can be improved. Examples of high elastic modulus fibers include carbon fiber, aramid fiber, glass fiber, and metal fiber (steel fiber). These high elastic modulus fibers can be used alone or in combination of two or more. Among these high elastic modulus fibers, carbon fiber and aramid fiber are preferred, and carbon fiber is most preferred. The proportion of the high elastic modulus fiber may be 10% by mass or more of the total fibers constituting the core wire, and is preferably 50% by mass or more, more preferably 80% by mass or more, more preferably 90% by mass or more, and most preferably 100% by mass.

[0162] The core wire may further contain other fibers in addition to the high elastic modulus fibers, as long as the effect of the present invention is not impaired. Examples of other fibers include synthetic fibers such as polyester fibers (polyalkylarylate fibers, polyparaphenylene naphthalate fibers), polybenzoxazole fibers, acrylic fibers, and aliphatic polyamide fibers. The proportion of other fibers in the total fibers constituting the core wire may be 50% by mass or less, preferably 20% by mass or less, and more preferably 10% by mass or less.

[0163] That is, the core wire of the present invention may contain these high elastic modulus fibers, but is preferably formed from these high elastic modulus fibers, and in high load transmission applications in rear wheel drive motorcycles, it is particularly preferable for it to be formed from carbon fibers.

[0164] Examples of carbon fibers include pitch-based carbon fibers, polyacrylonitrile (PAN)-based carbon fibers, phenolic resin-based carbon fibers, cellulose-based carbon fibers, and polyvinyl alcohol-based carbon fibers. Commercially available carbon fibers include "TORAYCA (registered trademark)" manufactured by Toray Industries, Inc., "Tenax (registered trademark)" manufactured by Toho Tenax Co., Ltd., and "DIALEAD (registered trademark)" manufactured by Mitsubishi Chemical Corporation. These carbon fibers can be used alone or in combination of two or more kinds. Among these carbon fibers, pitch-based carbon fibers and PAN-based carbon fibers are preferred, and PAN-based carbon fibers are particularly preferred.

[0165] In particular, for high-load transmission applications in rear-wheel drive motorcycles, multifilament carbon fiber yarns are preferably used. The multifilament carbon fiber yarns can be selected from multifilament yarns with different numbers of filaments, such as 6K and 12K. 6K represents a multifilament yarn with 6,000 filaments, and 12K represents a multifilament yarn with 12,000 filaments. The fineness of the 6K multifilament yarn is approximately 400 tex, and the fineness of the 12K multifilament yarn is approximately 800 tex.

[0166] If the fineness of the multifilament carbon fiber yarn is greater than 1000 tex, there is a risk of reduced resistance to bending fatigue. Conversely, if the fineness of the multifilament carbon fiber yarn is less than 300 tex, the material cost increases, and the number of first twisted yarns required to produce a core wire with sufficient tensile strength increases, leading to an increase in the number of work steps. In the present invention, by using carbon fibers having a small diameter of 1000 tex or less, a toothed belt that has excellent jumping resistance can be produced even when narrowed for application to high-load transmission applications in rear-wheel drive motorcycles.

[0167] Specific examples of the carbon fiber cord used for the core wire include the carbon fiber cords (twisted cords) shown in Table 1.

[0168] [Table 1]

[0169] The core wire diameter D, which means the average diameter (average wire diameter) of the core wire (or twisted cord), can be selected from the range of about 0.2 to 2.5 mm, for example, 0.8 to 2.4 mm. If the core wire diameter is too small, the core wire may stretch too much, which may cause tooth chipping (loss of teeth). If the core wire diameter is too large, the core wire may break due to a decrease in bending fatigue resistance.

[0170] In particular, in high load transmission applications such as rear wheel drive of motorcycles, it is preferable to adjust the core wire diameter D of the core wire made of carbon fiber in accordance with the tooth pitch.

[0171] In a toothed belt having a tooth pitch of 6 mm or more and less than 9.5 mm (e.g., 7 to 9 mm, particularly 8 mm), the core wire diameter D of the core wire made of carbon fiber may be adjusted, for example, to about 0.8 to 1.2 mm, preferably 0.9 to 1.1 mm, more preferably 0.9 to 1.05 mm, and even more preferably 0.9 to 1.0 mm.

[0172] In a toothed belt having a tooth pitch of 9.5 mm or more and less than 12.5 mm (for example, 10 to 12 mm, particularly 11 mm), the core wire diameter D of the core wire made of carbon fiber may be adjusted to, for example, 1.3 to 1.8 mm (particularly 1.4 to 1.8 mm).

[0173] Furthermore, in a toothed belt having a tooth pitch of 12.5 to 16 mm (e.g., 13 to 15 mm, particularly 14 mm), the core diameter D of the core wire made of carbon fiber may be adjusted, for example, to a range of about 1.7 to 2.4 mm (e.g., 1.9 to 2.4 mm), preferably 1.8 to 2.2 mm (particularly 1.9 to 2.2 mm), further preferably 1.8 to 2.1 mm, and even more preferably 1.8 to 2.0 mm.

[0174] The core wire pitch P, which means the pitch of the core wires (the distance between the centers of two adjacent core wires in the belt), can be selected, for example, from the range of about 0.2 to 2.5 mm, and is, for example, 0.9 to 2.5 mm, preferably 1.2 to 2.4 mm, further preferably 1.5 to 2.3 mm, even more preferably 1.9 to 2.2 mm, and most preferably 2.0 to 2.1 mm.

[0175] In particular, in high load transmission applications such as rear wheel drive of motorcycles, the cord pitch P of the cord made of carbon fiber is preferably adjusted in accordance with the tooth pitch.

[0176] In a toothed belt having a tooth pitch of 6 mm or more and less than 9.5 mm (e.g., 7 to 9 mm, particularly 8 mm), the core wire pitch P of the core wire made of carbon fiber may be adjusted to, for example, 0.9 to 1.3 mm, preferably 1.0 to 1.3 mm, more preferably 1.05 to 1.2 mm, and more preferably 1.1 to 1.15 mm.

[0177] In addition, in a toothed belt with a tooth pitch of 9.5 mm or more and less than 12.5 mm (for example, 10 to 12 mm, particularly 11 mm), the core wire pitch P of the core wire made of carbon fiber may be adjusted to, for example, 1.4 to 2.0 mm (particularly 1.5 to 1.9 mm).

[0178] Furthermore, in a toothed belt having a tooth pitch of 12.5 to 16 mm (e.g., 13 to 15 mm, particularly 14 mm), the core pitch P of the core wire made of carbon fiber may be adjusted to a range of, for example, about 1.8 to 2.5 mm (e.g., 2.0 to 2.5 mm), for example, 1.8 to 2.4 mm (particularly 2.0 to 2.3 mm), preferably 1.9 to 2.3 mm, and more preferably 1.9 to 2.2 mm.

[0179] In the present invention, by adjusting the core wire diameter D and core wire pitch P and controlling the X value (%) of the core wire arrangement density, a toothed belt suitable for high-load power transmission applications in rear-wheel drive motorcycles can be produced, and in particular, even when the width is narrowed, the elastic modulus of the belt can be increased to improve jumping resistance. In this application, the X value (%) of the arrangement density means "the proportion of areas without core wires (total spacing d) relative to the belt width W," or "the proportion of the total spacing d between adjacent core wires relative to the belt width W," and the smaller the X value, the denser the belt.

[0180] In detail, FIG. 6 is a drawing showing the belt width W, cord diameter D, cord interval d, and cord pitch P of the toothed belt of the present invention. As shown in FIG. 6, in the belt 1 equipped with the tooth cloth 2, the multiple cords 5 are arranged in the back rubber layer 6 at a predetermined interval d in the belt width direction, and this interval d includes not only the interval between adjacent cords 5, but also the interval between the cords 5 at both ends and the belt end (d at the left end in FIG. 6). The belt end means the end on the line connecting the centers of the cords 5 (the left end or the right end in FIG. 6). In other words, in the present application, the total value of the intervals d means the value obtained by subtracting the value of "total cord diameter D (cord diameter D × number of cords)" from the value W of the "belt width". Therefore, the X value (%) can be replaced with the relational expression between the cord diameter D and the cord pitch P as shown in the following formula.

[0181] X = (total of interval d / belt width W) x 100 = [(Belt width W - Core wire diameter D) / Belt width W] x 100 = {[Belt width W - (wire diameter D x number of wires)] / Belt width W} x 100 =〈{Belt width W - [Wire diameter D × (Belt width W / Wire pitch P)]} / Belt width W〉 ×100 = [1-(wire diameter D / wire pitch P)] x 100.

[0182] In this application, the belt width W, core wire diameter D, spacing d, and core wire pitch P are determined based on a cross-sectional view perpendicular to the length direction of the belt (cross-sectional view), and the core wire pitch P is the distance between the centers of adjacent core wires in the cross-sectional view, as shown in Figure 6.

[0183] The X value of the arrangement density of the core wires is, for example, 5 to 25%, preferably 5 to 20%, more preferably 5.1 to 15%, more preferably 5.2 to 13%, and most preferably 5.2 to 10%. If the X value is too small, the arrangement of the core wires becomes too dense (the interval d between adjacent core wires becomes too narrow), and rubber does not easily flow around the core wires during belt manufacturing, which may result in molding defects (the core wires are not supported by the rubber). On the other hand, if the X value is too large, the arrangement of the core wires becomes too sparse, and especially when the width is narrowed, the number of core wires becomes insufficient, resulting in insufficient belt elasticity, impairing meshing transmission performance (anti-jumping performance) and making it impossible to ensure durability.

[0184] In the present invention, by adjusting the twist factor of the twisted cord that constitutes the core wire, it is possible to produce a toothed belt suitable for high-load transmission applications in rear-wheel drive of motorcycles, and in particular, it is possible to improve the tension retention and bending fatigue resistance even when the width is narrowed.

[0185] The twist factor is a value that represents the angle that the fiber makes with respect to the length direction of the core wire, and serves as an index for comparing the twist strength of twisted yarns of different fineness. The larger the twist factor, the larger the angle that the fiber makes with respect to the length direction of the core wire, and the stronger the twist. In this application, the twist factor is calculated using the following formula, taking into account the specific gravity of the carbon fiber.

[0186] Twist factor = [number of twists (turns / m) × √fineness (tex)] / 960.

[0187] In the present invention, the twist coefficient of the Lang twisted cord or the ply twisted cord and the twist coefficient of the single twisted cord can be evaluated equally. Therefore, in the present application, the twist coefficient is used to include the twist coefficient of the single twisted cord. The twist coefficient of the core wire can be selected from a range of about 1.1 to 3 (particularly 1.1 to 2.7), for example, 1.1 to 2.5, preferably 1.2 to 2.5, further preferably 1.5 to 2.4, more preferably 1.7 to 2.3, and most preferably 1.8 to 2.2. If the twist coefficient is too small, there is a risk of reduced resistance to bending fatigue when applied to high load transmission applications in rear wheel drive of motorcycles, and conversely, if it is too large, there is a risk of reduced tension retention.

[0188] In particular, in high-load transmission applications such as rear-wheel drive motorcycles, the twist factor of the core wire made of carbon fiber is preferably adjusted according to the tooth pitch. In a toothed belt with a tooth pitch of 6 mm or more and less than 9.5 mm (e.g., 7 to 9 mm, particularly 8 mm), the upper twist factor of the core wire made of carbon fiber (particularly, the twist factor of the single-twist cord) is preferably adjusted to, for example, 1.1 to 2.0 (particularly, 1.5 to 1.8). In a toothed belt having a tooth pitch of 9.5 mm or more and less than 12.5 mm (e.g., 10 to 12 mm, particularly 11 mm), the upper twist factor of the core wire made of carbon fiber (particularly, the upper twist factor of the Lang twisted cord or the twist factor of the single twisted cord) is preferably adjusted to, for example, 1.2 to 2.5 (particularly, 1.7 to 2.5), and the lower twist factor of the core wire made of carbon fiber (particularly, the lower twist factor of the Lang twisted cord) is preferably adjusted to, for example, 0.7 to 1.8 (particularly, 0.7 to 1.5). Furthermore, in a toothed belt having a tooth pitch of 12.5 to 16 mm (e.g., 13 to 15 mm, particularly 14 mm), the upper twist factor of the core wire made of carbon fiber (particularly, the upper twist factor of the Lang twisted cord or the twist factor of the single twisted cord) is preferably adjusted to, for example, 1.4 to 2.4 (particularly, 1.7 to 2.4), and the lower twist factor of the core wire made of carbon fiber (particularly, the lower twist factor of the Lang twisted cord) is preferably adjusted to, for example, 0.7 to 1.8 (particularly, 0.7 to 1.5).

[0189] The core wire may be subjected to an adhesive treatment in order to enhance adhesion to the fourth crosslinked rubber composition. The adhesive treatment may be, for example, a method in which the twisted cord is immersed in a resorcin-formalin-latex treatment liquid (RFL treatment liquid) and then heated and dried to form a uniform adhesive layer on the surface of the twisted cord. The RFL treatment liquid is a mixture of a precondensate of resorcin and formalin mixed with latex, and the latex may be, for example, chloroprene rubber, styrene-butadiene-vinylpyridine terpolymer (VP latex), nitrile rubber, hydrogenated nitrile rubber, or the like. Furthermore, the adhesive treatment may be a method in which the twisted cord is pretreated with an epoxy compound or an isocyanate compound and then treated with the RFL treatment liquid.

[0190] [Elastic modulus of toothed belt] The elastic modulus of the toothed belt of the present invention can be controlled by adjusting the elastic modulus, twist coefficient, core wire diameter D, core wire pitch P, and arrangement density of the core wires, thereby making it possible to produce a toothed belt suitable for high-load transmission applications in rear-wheel drive of motorcycles. In other words, since the elastic modulus of a toothed belt is greatly affected by the elastic modulus of the arranged core wires (fibers), in the present invention, the elastic modulus of the belt is adjusted to an appropriate range suitable for the above-mentioned application by using a specific high elastic modulus fiber as the core wire and adjusting the arrangement density appropriately.

[0191] In this application, the elastic modulus (tensile elastic modulus) of the toothed belt is defined as Young's modulus E (N / mm 2 ), and the cross-sectional area of ​​the toothed belt is A (mm 2 ), the tensile force applied to the toothed belt is F (N), and the strain (rate of change in belt length) is ε (dimensionless), then EA is defined as the value (unit: N) of EA [E (Young's modulus of belt) × A (cross-sectional area of ​​belt)] and is derived as EA = F / ε.

[0192] The tensile stress of the toothed belt is σ(N / mm 2), there is a relationship of σ=F / A=E×ε, but since the toothed belt of the present invention is a composite of a rubber-like elastic body (rubber composition in this embodiment) and a core body (core wire in this embodiment), it is difficult to specify the cross-sectional area. Therefore, in this application, the belt elastic modulus (tensile elastic modulus) of the toothed belt of the present invention is defined as EA (N). In detail, the belt elastic modulus (tensile elastic modulus) of the toothed belt of the present invention can be measured as the tensile elastic modulus per mm by the method described in the examples below.

[0193] The elastic modulus (tensile elastic modulus) of the toothed belt of the present invention is, for example, 15 to 65 kN / mm, preferably 30 to 64 kN / mm, further preferably 40 to 63 kN / mm, more preferably 45 to 62 kN / mm, and most preferably 55 to 60 kN / mm. If the elastic modulus of the toothed belt is too small, when it is applied to a high load transmission application in the rear wheel drive of a motorcycle, there is a concern that the jumping resistance, tension maintenance, and tooth chipping resistance may decrease, and conversely, if it is too large, there is a concern that the bending fatigue resistance and belt installation ease may decrease.

[0194] In particular, in high load transmission applications such as rear wheel drive of motorcycles, the elastic modulus of the toothed belt is preferably adjusted according to the tooth pitch.

[0195] In a toothed belt with a tooth pitch of 6 mm or more and less than 9.5 mm (for example, 7 to 9 mm, particularly 8 mm), the elastic modulus (tensile elastic modulus) of the toothed belt is, for example, 15 to 20 kN / mm (particularly 16 to 19 kN / mm).

[0196] In addition, in a toothed belt having a tooth pitch of 9.5 mm or more and less than 12.5 mm (for example, 10 to 12 mm, particularly 11 mm), the elastic modulus (tensile elastic modulus) of the toothed belt is, for example, 42 to 60 kN / mm, preferably 42 to 50 kN / mm, and more preferably 42 to 48 kN / mm.

[0197] Furthermore, in a toothed belt having a tooth pitch of 12.5 to 16 mm (for example, 13 to 15 mm, particularly 14 mm), the elastic modulus (tensile elastic modulus) of the toothed belt is, for example, 50 to 65 kN / mm, preferably 53 to 65 kN / mm, and more preferably 54 to 60 kN / mm.

[0198] (Method of Manufacturing Toothed Belt) The toothed belt of the present invention may be produced, for example, by the following method (preforming method).

[0199] [First rubber layer precursor preparation step] When the tooth portion includes a tooth cloth, first, a tooth cloth precursor for forming the tooth cloth, and an uncrosslinked rubber sheet for forming a plurality of rubber layers are prepared, for example, a first rubber layer precursor which is an uncrosslinked rubber sheet for forming the first rubber layer (surface rubber layer), a second rubber layer precursor which is an uncrosslinked rubber sheet for forming the second rubber layer (inner rubber layer), and a back rubber layer precursor which is an unvulcanized rubber sheet for forming the back rubber layer.

[0200] In particular, the first rubber layer precursor is preferably subjected to the following first rubber layer precursor preparation step in order to orient the first short fibers in a predetermined direction.

[0201] In the first rubber layer precursor preparation step, the first short fibers can be oriented (aligned) in a predetermined direction during the process of preparing an uncrosslinked rubber sheet by rolling a rubber composition kneaded with a Banbury mixer or the like with a roll or a calendar. In more detail, a method for orienting the first short fibers in a predetermined direction (one direction of the sheet surface) can be a conventional method, for example, a method of rolling rubber into a sheet by passing it between a pair of calendar rolls having a predetermined gap therebetween to obtain a rolled sheet in which the first short fibers are oriented in the rolling direction.

[0202] When the second rubber layer and the back rubber layer contain short fibers (particularly when the second rubber layer contains second short fibers), the short fibers can be oriented in a similar manner.

[0203] [Preforming process] Next, a tooth cloth precursor for forming a tooth cloth is wound around the outer circumferential surface of a cylindrical mold having a plurality of grooves (concave strips) corresponding to the teeth of the toothed belt. Next, a first rubber precursor, which is an uncrosslinked rubber sheet for forming a first rubber layer (surface rubber layer), and a second rubber layer precursor, which is an uncrosslinked rubber sheet for forming a second rubber layer (internal rubber layer), are wound around the outer circumferential surface of the cylindrical mold with the orientation direction of the first short fiber of the first rubber precursor oriented in the belt longitudinal direction to form a laminate, and the laminate is pressurized from the outer circumferential side while being heated to a temperature at which the rubber composition is softened (for example, about 70 to 90°C) in a predetermined device, and the rubber composition of the uncrosslinked rubber sheet and the tooth cloth precursor are pressed into the grooves (concave strips) of the cylindrical mold to form teeth, thereby obtaining a preform in a semi-crosslinked state. In the process of forming the teeth by this pressing, the tooth cloth is stretched to follow the contour of the tooth cloth and disposed on the outermost surface, the first rubber layer is disposed on the inner side thereof along the contour of the tooth cloth, and the first short fibers are also aligned in the belt longitudinal direction and aligned in the direction along the contour of the tooth cloth, and the second rubber layer is disposed on the inner side thereof, forming a layer structure. If the tooth cloth does not include a tooth cloth, the first rubber precursor is wound around the outer peripheral surface of the cylindrical mold instead of the tooth cloth precursor.

[0204] The method for obtaining a semi-crosslinked preform may be a method in which, instead of using a cylindrical mold, a flat press mold (flat type) having a plurality of grooves (concave strips) corresponding to the teeth is used, and the rubber composition of the uncrosslinked rubber sheet and the tooth cloth precursor are pressed into the grooves (concave strips) of the flat mold by hot pressing in the above-mentioned procedure to form the teeth. In this method, after the preform is removed from the flat mold, the preform is wrapped around and attached (the teeth and grooves are fitted together) to a cylindrical mold having a plurality of grooves (concave strips) corresponding to the teeth, and then the next step is carried out.

[0205] [Crosslinking molding process] A twisted cord constituting a core wire is wound helically at a predetermined pitch (so as to have a predetermined pitch in the axial direction of the cylindrical mold) around the outer periphery of the obtained preform. Further, a back rubber layer precursor, which is an uncrosslinked rubber sheet that forms a back rubber layer, is wound around the outer periphery to form an uncrosslinked belt molded body (uncrosslinked laminate).

[0206] Next, the uncrosslinked belt molded body is placed on the outer periphery of a cylindrical mold, and then a rubber jacket, which is a vapor barrier material, is placed on the outside of the uncrosslinked belt molded body. The jacketed belt molded body and the cylindrical mold are then placed inside a crosslinking molding device such as a vulcanizer. When the belt molded body is heated and pressurized inside the crosslinking molding device, a desired shape is formed, and the components are bonded and integrally hardened by the crosslinking reaction of the uncrosslinked and semi-crosslinked rubber components contained in the belt molded body, forming a sleeve-shaped crosslinked molded body (crosslinked belt sleeve).

[0207] [Cutting process] Finally, the cross-linked belt sleeve is removed from the cylindrical mold and cut to a predetermined width to obtain a plurality of toothed belts. EXAMPLES

[0208] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.

[0209] [Rubber composition]

[0210] [Table 2]

[0211] [Table 3]

[0212] [Materials used in rubber composition] HNBR: Zeon Corporation "Zetpol2010", iodine value 11mg / 100mg HNBR containing unsaturated carboxylic acid metal salt: Zeoforte ZSC2295CX manufactured by Zeon Corporation, base HNBR: unsaturated carboxylic acid metal salt (mass ratio) = 100:110, iodine value of base HNBR 28mg / 100mg Nylon staple fiber: "Leona" manufactured by Asahi Kasei Corporation, polyamide 66, average fiber length 3 mm, average fiber diameter 27 μm Aramid short fiber 1: Teijin Co., Ltd. "Conex", average fiber length 3 mm, average fiber diameter 14 μm Aramid short fiber 2: "Twaron (registered trademark)" manufactured by Teijin Limited, average fiber length 3 mm, average fiber diameter 12 μm PBO staple fiber: "Zylon" manufactured by Toyobo Co., Ltd., average fiber length 3 mm, average fiber diameter 12 μm Stearic acid: "Camellia stearic acid" manufactured by NOF Corporation Carbon black SRF: "Seast S" manufactured by Tokai Carbon Co., Ltd., average particle size 66 nm, iodine adsorption capacity 26 mg / g Silica: "Ultrasil VN-3" manufactured by Evonik Degussa Japan Co., Ltd., specific surface area 155 to 195 m 2 / g Calcium carbonate: Maruo Calcium Co., Ltd. "Super #1500", average particle size 1.5 μm Zinc oxide: Sakai Chemical Industry Co., Ltd. "Zinc oxide type 2", average particle size 0.55 μm Anti-aging agent: p,p'-dioctyldiphenylamine, "Nonflex OD3" manufactured by Seiko Chemical Co., Ltd. Organic peroxide: 1,3-bis(t-butylperoxyisopropyl)benzene, theoretical active oxygen content 9.45% Co-crosslinking agent: N,N'-m-phenylenedimaleimide, "Valnoc PM" manufactured by Ouchi Shinko Chemical Co., Ltd. Plasticizer: "Adeka Cizer RS700" manufactured by ADEKA Corporation.

[0213] [Core] In Examples 1 to 33 and Comparative Examples 1 to 10, a carbon fiber cord (12K-1 / 0, tensile modulus 230 GPa) was produced by single-twisting a single 12K multifilament yarn (Toray Industries, Inc., "Torayca T700SC-12000," single yarn fineness 0.67 dtex, total fineness 800 tex) and then subjected to an adhesive treatment using an HNBR-based overcoat treatment agent to obtain a core wire with a core diameter of 1.1 mm.

[0214] In Examples 34 to 75 and Comparative Examples 11 to 13, various carbon fiber cords shown in Tables 13 to 16 and 18 to 20 were produced using the 12K multifilament yarn or 6K multifilament yarn, and various core wires were obtained by performing an adhesive treatment using an HNBR-based overcoat treatment agent.

[0215] [Tooth cloth and tooth cloth processing] A tooth cloth precursor was produced by immersing the woven fabric shown in Table 4 in the RFL treatment liquid and rubber paste. In detail, the RFL treatment was carried out using two types of RFL treatment liquid (RFL1, RFL2) shown in Table 5, and immersion treatment was carried out in the order of RFL1 and RFL2. Furthermore, the rubber paste treatment was also carried out using two types of rubber paste (rubber paste 1, rubber paste 2) shown in Table 6, and immersion treatment was carried out in the order of rubber paste 1 and rubber paste 2.

[0216] [Table 4]

[0217] *1: PTFE fiber [Toyoflon 1330dtex, manufactured by Toray Industries, Inc.] *2: Polyester fiber [Unitika Ltd.'s "Cornetta", a core-sheath type composite fiber with a core melting point of 256°C and a sheath melting point of 160°C]

[0218] [Table 5]

[0219] [Table 6]

[0220] [Preparation of uncrosslinked rubber sheet] As the uncrosslinked rubber sheet for forming the teeth and back (back rubber layer), each rubber composition of the formulation shown in Tables 2 and 3 was kneaded using a Banbury mixer, and the kneaded rubber obtained was rolled to a predetermined thickness using a calendar roll to prepare an uncrosslinked rubber sheet. The short fibers contained in the uncrosslinked rubber sheet were oriented in the rolling direction. In this application, each rubber composition is represented by R1 to R30.

[0221] [Hardness (Type D)] The uncrosslinked rubber sheet was press-heated at 165°C for 30 minutes to produce a crosslinked rubber sheet (100mm x 100mm x 2mm thick). A laminate of three crosslinked rubber sheets was used as a sample, and the hardness (type D) of the crosslinked rubber sheet was measured using a type D durometer in accordance with the spring durometer hardness test specified in JIS K 6253 (2012) (vulcanized rubber and thermoplastic rubber - Determination of hardness).

[0222] [Tensile strength] The uncrosslinked rubber sheet was press-heated at a temperature of 165°C for 30 minutes to prepare a crosslinked rubber sheet (100mm x 100mm x 2mm thick), and a dumbbell-shaped (5-type) test specimen was prepared according to JIS K 6251 (2017). For samples containing short fibers, dumbbell-shaped test specimens were taken so that the short fiber arrangement direction (parallel to the grain direction) was the tensile direction. Then, both ends of the test specimen were held with a chuck (gripping tool), and the test specimen was pulled until it broke at a speed of 50mm / min. The maximum tensile force recorded when the test specimen was divided by the initial cross-sectional area of ​​the test specimen (tensile strength T) was defined as the tensile strength. The tensile strength of each rubber composition is shown in Tables 2 and 3.

[0223] [Tensile modulus] Dumbbell-shaped test pieces (size 5) were prepared in accordance with JIS K 6251 (2017) in the same manner as for the tensile strength. For samples containing short fibers, dumbbell-shaped test pieces were taken so that the tensile direction was perpendicular (perpendicular to the grain) to the arrangement direction of the short fibers (parallel to the grain). Then, both ends of the test piece were held with a chuck (gripping tool) and the test piece was pulled at a speed of 50 mm / min. The tensile force at a given elongation (2%) was divided by the initial cross-sectional area of ​​the test piece (tensile stress at 2% elongation), which was taken as the tensile modulus. The tensile modulus of each rubber composition is shown in Tables 2 and 3.

[0224] Examples 1 to 33 and Comparative Examples 1 to 10 [Manufacturing of toothed belts] In Examples 1 to 33 and Comparative Examples 1 to 10, as shown below, using the preforming method described in this embodiment, toothed belts having a total thickness of 5.6 mm, tooth type G8M, tooth height (including tooth cloth) of 3.5 mm, tooth pitch 8 mm, number of teeth 140, circumference length 1120 mm, and width 12 mm were produced.

[0225] For the toothed belts produced in Examples 1 to 33 and Comparative Examples 1 to 10, the configurations (layer structures) of the toothed portions and the rubber compositions used in each rubber layer are shown in Tables 8 to 12.

[0226] Comparative Example 1 A tooth cloth precursor for forming the tooth cloth, an uncrosslinked rubber sheet for forming the first rubber layer (R3, sheet thickness 0.70 mm), and an uncrosslinked rubber sheet for forming the second rubber layer (R2, sheet thickness 1.00 mm) were layered in that order on a press mold (flat) having a plurality of grooves (concave strips) corresponding to the teeth of the toothed belt, and pressed for 160 seconds under conditions of a temperature of 90°C and a press pressure (surface pressure) of 20.2 MPa to produce a semi-crosslinked preform.

[0227] Next, the preform was wound around a cylindrical mold having a plurality of grooves (concave strips) corresponding to the teeth and attached (the teeth and grooves were engaged), and the twisted cord constituting the core wire was spun in a spiral shape on the outer circumferential surface of the preform (tension: 150-250 N / piece, spinning pitch: 1.25 mm, spinning speed: 1.5 m / s). Furthermore, an uncrosslinked rubber sheet (R30, sheet thickness 0.90 mm) forming the back rubber layer was wound around the outer circumferential side to form an uncrosslinked belt molded body (uncrosslinked laminate). The uncrosslinked rubber sheet was wound so that the orientation direction of the short fibers contained in the sheet was the belt longitudinal direction.

[0228] Next, crosslinking molding was carried out for 40 minutes using a vulcanizer under conditions of a heating temperature of 179° C. and a steam pressure of 0.83 MPa to produce a crosslinked molded product (crosslinked belt sleeve).

[0229] Finally, the crosslinked belt sleeve was removed from the cylindrical mold and cut to a width of 12 mm to obtain a toothed belt.

[0230] (Comparative Examples 2 to 5) A toothed belt was produced in the same manner as in Comparative Example 1, except that R4 was used in Comparative Example 2, R5 in Comparative Example 3, R6 in Comparative Example 4, and R7 in Comparative Example 5 were used as the uncrosslinked rubber sheet forming the first rubber layer.

[0231] (Examples 1 to 6) A toothed belt was produced in the same manner as in Comparative Example 1, except that R8 was used in Example 1, R9 in Example 2, R10 in Example 3, R11 in Example 4, R12 in Example 5, and R13 in Example 6 as the uncrosslinked rubber sheet forming the first rubber layer.

[0232] Comparative Example 6 A toothed belt was produced in the same manner as in Comparative Example 1, except that the uncrosslinked rubber sheet forming the teeth portion was only one type, R2 (sheet thickness 1.70 mm).

[0233] Comparative Example 7 A toothed belt was produced in the same manner as in Comparative Example 1, except that the uncrosslinked rubber sheet forming the teeth portion was only one type, R10 (sheet thickness 1.70 mm).

[0234] Comparative Example 8 A toothed belt was produced in the same manner as in Example 3, except that the uncrosslinked rubber sheet forming the first rubber layer was R2 (sheet thickness 0.85 mm) and the uncrosslinked rubber sheet forming the second rubber layer was R10 (sheet thickness 0.85 mm).

[0235] Example 7 A toothed belt was produced in the same manner as in Example 3, except that the thickness of the uncrosslinked rubber sheet forming the first rubber layer was 0.20 mm, and the thickness of the uncrosslinked rubber sheet forming the second rubber layer was 1.50 mm.

[0236] Example 8 A toothed belt was produced in the same manner as in Example 3, except that the thickness of the uncrosslinked rubber sheet forming the first rubber layer was 0.35 mm, and the thickness of the uncrosslinked rubber sheet forming the second rubber layer was 1.35 mm.

[0237] Example 9 A toothed belt was produced in the same manner as in Example 3, except that the thickness of the uncrosslinked rubber sheet forming the first rubber layer was 1.00 mm, and the thickness of the uncrosslinked rubber sheet forming the second rubber layer was 0.70 mm.

[0238] Example 10 A toothed belt was produced in the same manner as in Example 3, except that the thickness of the uncrosslinked rubber sheet forming the first rubber layer was 1.35 mm, and the thickness of the uncrosslinked rubber sheet forming the second rubber layer was 0.35 mm.

[0239] (Examples 11 to 15) A toothed belt was produced in the same manner as in Example 3, except that R14 was used in Example 11, R15 in Example 12, R16 in Example 13, R17 in Example 14, and R18 in Example 15 were used as the uncrosslinked rubber sheet forming the first rubber layer.

[0240] (Examples 16 to 21) A toothed belt was produced in the same manner as in Example 3, except that R20 was used in Example 16, R21 in Example 17, R22 in Example 18, R23 in Example 19, R24 in Example 20, and R25 in Example 21 were used as the uncrosslinked rubber sheet forming the first rubber layer.

[0241] Example 22 A toothed belt was produced in the same manner as in Example 3, except that the uncrosslinked rubber sheet forming the first rubber layer was R14 (sheet thickness 0.20 mm) and the uncrosslinked rubber sheet forming the second rubber layer was R2 (sheet thickness 1.50 mm).

[0242] (Example 23) A toothed belt was produced in the same manner as in Example 3, except that the uncrosslinked rubber sheet forming the first rubber layer was R17 (sheet thickness 1.00 mm) and the uncrosslinked rubber sheet forming the second rubber layer was R2 (sheet thickness 0.70 mm).

[0243] Example 24 A toothed belt was produced in the same manner as in Example 3, except that the uncrosslinked rubber sheet forming the first rubber layer was R17 (sheet thickness 1.35 mm) and the uncrosslinked rubber sheet forming the second rubber layer was R2 (sheet thickness 0.35 mm).

[0244] (Examples 25 to 27, Comparative Example 9) A toothed belt was produced in the same manner as in Example 3, except that the uncrosslinked rubber sheet forming the second rubber layer was R1 in Example 25, R4 in Example 26, R5 in Example 27, and R7 in Comparative Example 9.

[0245] (Examples 28 to 29) A toothed belt was produced in the same manner as in Example 25, except that the uncrosslinked rubber sheet forming the first rubber layer was R8 in Example 28 and R13 in Example 29.

[0246] (Example 30, Comparative Example 10) A toothed belt was produced in the same manner as in Comparative Example 9, except that R8 was used in Comparative Example 10 and R13 was used in Example 30 as the uncrosslinked rubber sheet forming the first rubber layer.

[0247] (Example 31) A toothed belt was produced in the same manner as in Example 3, except that the uncrosslinked rubber sheet forming the first rubber layer was R27, and the uncrosslinked rubber sheet forming the second rubber layer was R26.

[0248] (Examples 32 and 33) In Examples 32 and 33, toothed belts were produced in the same manner as in Examples 3 and 14, respectively, except that preforms were produced without using a tooth cloth precursor for forming the tooth cloth. These toothed belts were in a form in which no tooth cloth was provided on the surfaces of the teeth and tooth bottoms of the belt, and the tooth height was 3.5 mm (excluding the tooth cloth).

[0249] [Bending stiffness test] (Bending stiffness test conditions) For toothed belts, the bending stiffness E of toothed belts was measured by bending test using an Olsen bending tester according to JIS K 7106 (1995). r The moment of inertia I of the toothed belt is calculated by the following formula (1) using the obtained Er. r Multiplying this by the following formula (2), the bending stiffness E of the toothed belt is calculated. r I r was calculated. The size of the toothed belt test piece was length: 80 mm, width: 12 mm, back thickness: 2.1 mm, distance between supports S was 25.4 mm, and pendulum moment M at 100% load scale was 0.343 N·m. The test was performed under conditions of temperature 23±2°C and humidity 65±5%. The smaller the bending stiffness value, the more excellent the bending (flexibility). The criteria for bending stiffness are as follows:

[0250] I r = b × h 3 / 12 (1) [In the formula, Ir : Moment of inertia of test piece (mm 4 ), b: width of the test piece (mm), h: thickness of the back of the test piece (mm)]

[0251] E r I r =[(S×M) / 300]×[N / (D×0.01745)] (2) [In the formula, E r : Bending stiffness of test piece (N / mm 2 ), Ir: moment of inertia of the test piece (mm 4 ), S: distance between supports (mm), M: pendulum moment (N m), D: bending angle (degrees) (1 degree = π / 180 = 0.01745 radians), N: load scale reading (%) corresponding to bending angle (degrees)

[0252] (Bending rigidity criteria) A: Bending rigidity is less than 700MPa (pass) b: Bending rigidity is 700MPa or more and less than 800MPa (pass) c: Bending rigidity is 800 MPa or more (failed).

[0253] The test results for the toothed belts of Examples 1 to 33 and Comparative Examples 1 to 10 are shown in Tables 8 to 12.

[0254] [Tooth stiffness test] (Tooth stiffness test conditions) As shown in Figure 7, the toothed portion of the toothed belt 1 was hooked on the protrusion 21a of a tooth shearing jig (rigid body simulating the tooth shape of a toothed pulley) 21, and one tooth was pressed with a constant pressure (tightening torque of 0.98 cN·m per 1 mm width) while being pulled at a speed of 1 mm / min by an autograph. The tooth load per 12 mm width relative to the displacement was defined as the tooth stiffness (tooth stiffness) and evaluated. The tooth load value relative to the displacement was determined by linear approximation in the tooth load range of 50 to 400 N, as shown in Figure 8, using the third cycle where the value stabilized. A higher tooth stiffness value indicates better stiffness (resistance to deformation) of the toothed portion. The criteria for tooth stiffness are as follows:

[0255] (Criteria for determining tooth stiffness) A: Tooth stiffness is 1300N / mm or more (passed) b: Tooth stiffness is 1100N / mm or more and less than 1300N / mm (pass) c: Tooth stiffness is less than 1100N / mm (failed)

[0256] The test results for the toothed belts of Examples 1 to 33 and Comparative Examples 1 to 10 are shown in Tables 8 to 12.

[0257] [Jumping test] (Driving test conditions) Using a two-axis torque measuring tester, a toothed belt was wound between a driving pulley (number of teeth: 22) and a driven pulley (number of teeth: 22), and the center distance of the pulleys was adjusted so that the belt tension was 230N.The driving pulley was then rotated at 1,800 rpm to run the belt while continuously increasing the load on the driven pulley, and the load torque applied to the driven pulley when jumping (tooth skipping) occurred was measured as the jumping torque.The jumping torque value is used as an index of jumping resistance, and the higher the jumping torque value, the better the toothed belt is at preventing tooth skipping.

[0258] The jumping torque values ​​of each Example and Comparative Example are shown as relative values, with the jumping torque value (112 N m) of Comparative Example 2, which has a small proportion of short fibers in the first rubber layer (2 parts by mass) and has the best running durability among the comparative examples set as 1.00. A value of 1.00 or less indicates that the reinforcing effect of the toothed belt of Comparative Example 2 is not apparent, and a value exceeding 1.00 indicates that the stiffness (resistance to deformation) of the teeth has been improved by the reinforcing effect, and the higher this value, the greater the reinforcing effect.

[0259] (Jumping test criteria) A: Jumping torque exceeds 1.00 (pass) b: Jumping torque is 1.00 (pass) c: Jumping torque is 0.95 or more and less than 1.00 (pass) d: Jumping torque is less than 0.95 (fail).

[0260] [Durability test] (Driving test conditions) The toothed belt was attached to a biaxial running test machine equipped with a driving pulley (number of teeth: 22) and a driven pulley (number of teeth: 22), and the running life was measured as the running time until the toothed belt failed (loss of teeth). The installation tension of the toothed belt was 230N, the rotation speed of the driving pulley was 1800rpm, the load on the driven pulley was 9.0kW, and the ambient temperature was 25℃ (room temperature).

[0261] With regard to the running time until failure (hereinafter referred to as running time), the running time of Comparative Example 2, which contains a small proportion of short fibers (2 parts by mass) in the first rubber layer and has the best running durability among the comparative examples (159 hours), is set to 1.00, and the running times of each Example and Comparative Example are shown as relative values. If this value is 1.00 or less, it indicates that the reinforcing effect of Comparative Example 2 is not exhibited, and if it exceeds 1.00, it indicates that the reinforcing effect has improved running durability, and it can be said that the higher this value is, the higher the reinforcing effect is exhibited.

[0262] (Durability test criteria) a: Running time to failure is 1.25 or more (with reinforcement effect) b: Running time to failure is 1.10 or more and less than 1.25 (with reinforcement effect) c: Running time to failure is greater than 1.00 and less than 1.10 (with reinforcement effect) d: Run time to failure is less than 1.00 (no reinforcement effect).

[0263] [Overall Judgment] Considering the level of the reinforcing effect in terms of both jumping torque and running durability compared to Comparative Example 2 serving as the standard, a comprehensive evaluation was made according to the criteria shown in Table 7.

[0264] [Table 7]

[0265] Tables 8 to 12 show the test results for the toothed belts of Examples 1 to 33 and Comparative Examples 1 to 10. Furthermore, cross-sectional views of the toothed portions of the toothed belts of Examples 3, 8, and 9 and Comparative Examples 6 to 8 are shown in FIG.

[0266] [Table 8]

[0267] [Table 9]

[0268] [Table 10]

[0269] [Table 11]

[0270] [Table 12]

[0271] (Comparative Examples 1 to 5) Comparative Example 1 is an example of a toothed belt in which the tooth portion has a two-layer structure consisting of a first rubber layer (surface rubber layer) arranged on the surface side along the contour of the tooth portion and a second rubber layer (internal rubber layer) arranged inside the tooth portion, the first rubber layer being made of R3 (crosslinked rubber) with a tensile modulus of 6.0 MPa, and the second rubber layer being made of R2 (crosslinked rubber) with a tensile modulus of 3.8 MPa. The ratio of the tensile modulus of the first rubber layer to the tensile modulus of the second rubber layer is 1.6. Hereinafter, this ratio (tensile modulus of the first rubber layer / tensile modulus of the second rubber layer) will be referred to as the "ratio of the tensile modulus of the two layers."

[0272] Comparative Examples 2 to 5 are examples in which the tensile modulus was increased by increasing the amount of the first co-crosslinking agent in the first rubber layer of Comparative Example 1. With the increase in the amount, the tensile modulus increased to 9.4 MPa in Comparative Example 2, 10.9 MPa in Comparative Example 3, 13.7 MPa in Comparative Example 4, and 16.8 MPa in Comparative Example 5.

[0273] As a result, the bending rigidity was 602 N / mm (Comparative Example 1: judged as a), 652 N / mm (Comparative Example 2: judged as a), 660 N / mm (Comparative Example 3: judged as a), 676 N / mm (Comparative Example 4: judged as a), and 724 N / mm (Comparative Example 5: judged as b), all of which were at the pass level.

[0274] In addition, the tooth rigidity was 1,185 MPa (Comparative Example 1: grade b), 1,362 MPa (Comparative Example 2: grade a), 1,410 MPa (Comparative Example 3: grade a), 1,454 MPa (Comparative Example 4: grade a), and 1,527 MPa (Comparative Example 5: grade a), all of which were within the acceptable level.

[0275] Regarding dynamic performance, the jumping torque (relative value) was 0.95 (Comparative Example 1: judged as c), 1.00 (Comparative Example 2: judged as b), 1.03 (Comparative Example 3: judged as a), 1.06 (Comparative Example 4: judged as a), and 1.07 (Comparative Example 5: judged as a), all of which were within the acceptable level, and increased as the tensile modulus of the first rubber layer increased, following the same trend as the tooth stiffness.

[0276] However, the durability running (running time until failure (relative value)) was 0.53 (Comparative Example 1: d grade), 1.00 (Comparative Example 2: d grade), 0.80 (Comparative Example 3: d grade), 0.86 (Comparative Example 4: d grade), and 0.69 (Comparative Example 5: d grade), and the overall grade was unacceptable (D rank). In these examples, it can be assumed that the microcracks that had developed during long-term running had grown and caused the chipped teeth.

[0277] (Examples 1 to 6) Example 1 is an example in which the content of the co-crosslinking agent in the first rubber layer of Comparative Example 1 is low at 1 part by mass (the same amount as in the second rubber layer), but the amount of the first short fibers is increased to 20 parts by mass. That is, the first rubber layer is formed of R8 (crosslinked rubber) with a tensile modulus of 5.3 MPa, and the second rubber layer is formed of R2 (crosslinked rubber) with a tensile modulus of 3.8 MPa, and the ratio of the tensile moduli of the two layers is 1.4.

[0278] Regarding dynamic performance, the jumping torque (relative value) was at the same level as Comparative Example 1, which was 0.95 (rating c). However, the durability driving (driving time until failure (relative value)) was improved to 1.43 (rating a) compared to 0.53 (rating c) in Comparative Example 1, resulting in an overall rating of pass (rank C).

[0279] Example 2 is an example in which the amount of the first short fibers is increased to 20 parts by mass while keeping the content of the co-crosslinking agent the same (3 parts by mass) in the first rubber layer of Comparative Example 1. That is, the first rubber layer is formed of R9 (crosslinked rubber) with a tensile modulus of 9.0 MPa, and the second rubber layer is formed of R2 (crosslinked rubber) with a tensile modulus of 3.8 MPa, and the ratio of the tensile moduli of the two layers is 2.4.

[0280] Example 3 is an example in which the amount of the first short fibers was increased to 20 parts by mass while keeping the content of the co-crosslinking agent the same (6 parts by mass) in the first rubber layer of Comparative Example 2. That is, the first rubber layer was formed of R10 (crosslinked rubber) with a tensile modulus of 14 MPa, and the second rubber layer was formed of R2 (crosslinked rubber) with a tensile modulus of 3.8 MPa, and the ratio of the tensile moduli of the two layers was 3.7.

[0281] Example 4 is an example in which the amount of the first short fibers was increased to 20 parts by mass while keeping the content of the co-crosslinking agent the same (8 parts by mass) in the first rubber layer of Comparative Example 3. That is, the first rubber layer was formed of R11 (crosslinked rubber) with a tensile modulus of 14.3 MPa, and the second rubber layer was formed of R2 (crosslinked rubber) with a tensile modulus of 3.8 MPa, and the ratio of the tensile moduli of the two layers was 3.8.

[0282] Example 5 is an example in which the amount of the first short fibers was increased to 20 parts by mass while the content of the co-crosslinking agent was kept the same (11 parts by mass) in the first rubber layer of Comparative Example 4. That is, the first rubber layer was formed of R12 (crosslinked rubber) with a tensile modulus of 19.2 MPa, and the second rubber layer was formed of R2 (crosslinked rubber) with a tensile modulus of 3.8 MPa, and the ratio of the tensile moduli of the two layers was 5.1.

[0283] Example 6 is an example in which the amount of the first short fibers was increased to 20 parts by mass while the content of the first co-crosslinking agent was kept the same (14 parts by mass) in the first rubber layer of Comparative Example 5. That is, the first rubber layer was formed of R13 (crosslinked rubber) with a tensile modulus of 23.5 MPa, and the second rubber layer was formed of R2 (crosslinked rubber) with a tensile modulus of 3.8 MPa, and the ratio of the tensile moduli of the two layers was 6.2.

[0284] When Examples 2 to 6 are compared with the corresponding Comparative Examples (comparisons in which the content of the first co-crosslinking agent is the same but the amount of the first short fiber is increased), in all comparisons, the jumping torque (relative value) was equal to or greater than that of the Comparative Examples and was rated as A, and the durability running (running time until failure (relative value)) was also improved to 1.64 (Example 2; rated as A), 2.08 (Example 3; rated as A), 1.50 (Example 4; rated as A), 1.55 (Example 5; rated as A), and 1.54 (Example 6; rated as A), compared to the Comparative Examples, which were at the failing level. The overall rating was pass (Rank A).

[0285] In particular, Example 3 (R10, 6 parts by mass of the first co-crosslinking agent) showed excellent results in terms of both jumping torque and durable running, and it was found that a further increase in the amount of the first co-crosslinking agent did not improve the running life. From the above results, it was confirmed that an increase in the amount of the first short fibers is effective in improving durability (lengthening the life).

[0286] (Comparative Examples 6 to 8) Comparative Example 6 is an example of a toothed belt in which the entire rubber layer forming the teeth portion is formed only from R2 (crosslinked rubber) having a tensile modulus of elasticity of 3.8 MPa (relatively low modulus of elasticity) which formed the second rubber layer in Examples 1 to 6. The bending rigidity was 553 MPa (a judgment), which was better than that of the Examples, but the tooth rigidity was 1,092 N / mm (c judgment), which was unacceptable. As for the dynamic performance, the jumping torque (relative value) was 0.90 (d judgment), and the durability running (running time (relative value) until failure) was also 0.33 (d judgment), resulting in an overall unacceptable judgment (D rank).

[0287] Comparative Example 7 is an example of a toothed belt in which the entire rubber layer forming the teeth portion is formed only from R10 (crosslinked rubber) with a tensile modulus of elasticity of 14 MPa (relatively high modulus of elasticity) that formed the first rubber layer of Example 3. The tooth rigidity was 1,750 N / mm (a judgment), which was better than that of the Examples, but the bending rigidity was 825 MPa (c judgment), which was unacceptable. As for the dynamic performance, the jumping torque (relative value) was 1.35 (a judgment), but the durability running (running time until failure (relative value)) was 0.43 (d judgment), and the overall judgment was unacceptable (D rank).

[0288] In Comparative Example 8, the tooth portion has a two-layer structure of a first rubber layer and a second rubber layer, as in the Example, but the magnitude of the elastic modulus of the first rubber layer and the second rubber layer is reversed. That is, R2 (crosslinked rubber) with a tensile modulus of 3.8 MPa (relatively low elastic modulus) was used for the first rubber layer, and R10 (crosslinked rubber) with a tensile modulus of 14 MPa (relatively high elastic modulus) was used for the second rubber layer. In addition, the ratio of the area occupied by the first rubber layer to the total rubber layers constituting the tooth portion was set to 50% in a cross-sectional view of the tooth portion. As a result, the tooth rigidity was 1,275 N / mm (judgement b), which was at an acceptable level, but the bending rigidity was 820 MPa (judgement c), which was unacceptable. As for the dynamic performance, the jumping torque (relative value) was 1.07 (judgement a), but the durability running (running time until failure (relative value)) was 0.75 (judgement d), and the overall judgment was unacceptable (D rank).

[0289] When the entire tooth portion is formed from a rubber layer with a low elastic modulus as in Comparative Example 6, the rigidity (resistance to deformation) of the tooth portion is insufficient, and when the entire tooth portion is formed from a rubber layer with a high elastic modulus as in Comparative Example 7, the flexibility (low bending rigidity) is insufficient. Furthermore, when the tooth portion is made of two layers but the inner portion is formed from a rubber layer with a high elastic modulus rather than the surface portion as in Comparative Example 8, the flexibility (low bending rigidity) is insufficient and the rigidity (resistance to deformation) of the tooth portion is also reduced. Furthermore, since there is no first rubber layer in which a predetermined amount of short fibers are oriented, durability is low.

[0290] In contrast, the embodiment of the present invention has a tooth portion with a rigidity (high elastic modulus) that can withstand use under conditions of higher loads, and is a well-balanced embodiment that can achieve both the rigidity (resistance to deformation) and flexibility (low bending rigidity: flexibility) of the tooth portion, which are in a trade-off relationship, and also has excellent durability.

[0291] (Examples 7 to 10) In comparison with the toothed belt of Example 3 in which the first rubber layer was formed of R10 (crosslinked rubber) having a tensile modulus of 14 MPa and the second rubber layer was formed of R2 (crosslinked rubber) having a tensile modulus of 3.8 MPa, Examples 7 to 10 are examples of toothed belts in which the ratio of the area occupied by the first rubber layer to all of the rubber layers constituting the toothed portion is varied in a cross-sectional view of the toothed portion.

[0292] In Examples 7 to 10 and Example 3, when viewed in cross section of the tooth portion, the area ratio of the first rubber layer to all rubber layers constituting the tooth portion is 10% (Example 7), 20% (Example 8), 40% (Example 3), 60% (Example 9), and 80% (Example 10).

[0293] As a result, the tooth rigidity was 1,275 N / mm (Example 7: graded b), 1,347 N / mm (Example 8: graded a), 1,442 N / mm (Example 3: graded a), 1,527 N / mm (Example 9: graded a), and 1,561 N / mm (Example 10: graded a), all of which were within the acceptable level and improved as the area proportion of the first rubber layer increased.

[0294] On the other hand, the bending rigidity was 601 MPa (Example 7: grade a), 633 MPa (Example 8: grade a), 671 MPa (Example 3: grade a), 692 MPa (Example 9: grade a), and 743 MPa (Example 10: grade b), all of which were within the acceptable level and increased as the area proportion of the first rubber layer increased.

[0295] Regarding dynamic performance, the jumping torque (relative value) was 1.00 (Example 7: judged as b), 1.10 (Example 8: judged as a), 1.11 (Example 3: judged as a), 1.26 (Example 9: judged as a), and 1.31 (Example 10: judged as a), all of which were within the acceptable level, and increased as the area proportion of the first rubber layer increased, following the same trend as the tooth stiffness.

[0296] Furthermore, the durability running (running time until failure (relative value)) was 1.41 (Example 7: grade a), 1.82 (Example 8: grade a), 2.08 (Example 3: grade a), 1.69 (Example 9: grade a), and 1.07 (Example 10: grade c), all of which were within the acceptable level, and the area ratio of the first rubber layer increased particularly in the range of 20 to 60%.

[0297] In the overall evaluation above, the toothed belts of Examples 7 to 10 were of an acceptable standard (A to C rank).

[0298] (Examples 11 to 15) Among Examples 1 to 6, Example 3 (20 parts by mass of the first short fiber, 6 parts by mass of the first co-crosslinking agent, and a ratio of the area of ​​the first rubber layer to the total area of ​​the rubber layers constituting the tooth portion of 40% in a cross-sectional view of the tooth portion) had the most excellent running durability, whereas Examples 11 to 15 are examples of toothed belts using rubber compositions in which the amount of the first short fiber contained in the first rubber layer is varied. The first rubber layer was formed using R14 (5 parts by mass of short fibers, tensile modulus of elasticity 10.8 MPa) in Example 11, R15 (10 parts by mass of short fibers, tensile modulus of elasticity 12.6 MPa) in Example 12, R10 (20 parts by mass of short fibers, tensile modulus of elasticity 14 MPa) in Example 3, R16 (30 parts by mass of short fibers, tensile modulus of elasticity 13.7 MPa) in Example 13, R17 (50 parts by mass of short fibers, tensile modulus of elasticity 14.0 MPa) in Example 14, and R18 (60 parts by mass of short fibers, tensile modulus of elasticity 13.9 MPa) in Example 15. Note that the rubber composition of R19 (65 parts by mass of short fibers) could not be kneaded, so a toothed belt could not be produced.

[0299] As a result, the tooth rigidity was 1,271 N / mm (Example 11: graded b), 1,367 N / mm (Example 12: graded a), 1,442 N / mm (Example 3: graded a), 1,430 N / mm (Example 13: graded a), 1,432 N / mm (Example 14: graded a), and 1,425 N / mm (Example 15: graded a), all of which were within the acceptable level.

[0300] On the other hand, the bending rigidity increased as the elastic modulus of the first rubber layer increased, to 648 MPa (Example 11: judged as a), 662 MPa (Example 12: judged as a), 671 MPa (Example 3: judged as a), 687 MPa (Example 13: judged as a), 706 MPa (Example 14: judged as b), and 713 MPa (Example 15: judged as b).

[0301] Regarding dynamic performance, the jumping torque (relative value) was 1.03 (Example 11: judged as a), 1.05 (Example 12: judged as a), 1.11 (Example 3: judged as a), 1.07 (Example 13: judged as a), 1.07 (Example 14: judged as a), and 1.06 (Example 15: judged as a), all of which were within the acceptable level, showing the same trend as the tooth rigidity.

[0302] On the other hand, the durability driving (driving time until failure (relative value)) was 1.24 (Example 11: grade b), 1.86 (Example 12: grade a), 2.08 (Example 3: grade a), 1.30 (Example 13: grade a), 1.25 (Example 14: grade a), and 1.21 (Example 15: grade b), all of which were within the acceptable level.

[0303] From the above overall judgment, the toothed belts of Examples 3 and 11 to 15 were at a high level of pass (A or B rank) in that they exhibited reinforcing effects in both jumping torque and running durability. In particular, Example 12 (short fiber 10 parts by mass, tensile modulus 12.6 MPa) and Example 3 (short fiber 20 parts by mass, tensile modulus 14.0 MPa) were excellent in jumping torque and exhibited a significant effect in running durability (long life). In particular, Example 3 had a significantly large tensile strength of the rubber composition (R10), and thus exhibited a large reinforcing effect. On the other hand, Examples 13 to 15, in which the amount of the first short fiber was further increased, did not exhibit the same long life effect as Examples 12 and 3, and therefore, as a reinforcing effect of the first short fiber, a content of about 10 to 30 parts by mass with a peak at about 20 parts by mass can be said to be a particularly suitable range.

[0304] From the above results, it can be said that the preferable range of the physical property value of the first rubber layer is 4 to 25 MPa (especially 10 to 15 MPa) in the belt width (anti-grain) direction in terms of tensile elasticity, and the preferable range of the proportion of short fibers contained in the first rubber layer is 5 to 60 parts by mass (especially 10 to 30 parts by mass).

[0305] Example 16 In comparison with the configuration of Example 1 (R8: 20 parts by mass of first short fiber, 1 part by mass of first co-crosslinking agent), Example 16 is an example of a toothed belt in which the amount of the first short fiber contained in the first rubber layer is reduced to 10 parts by mass. This is an example in which the contents of the first short fiber and the first co-crosslinking agent, which affect the elastic modulus (reinforcement) of the first rubber layer, are verified at a level near the lower limit of the reinforcing effect. That is, the first rubber layer is formed of R20 (crosslinked rubber) with a tensile modulus of 4.3 MPa, and the second rubber layer is formed of R2 (crosslinked rubber) with a tensile modulus of 3.8 MPa, and the ratio of the tensile modulus of the two layers is 1.1. As for the dynamic performance, the jumping torque (relative value) was at the same level as Comparative Example 1, which was 0.95 (c judgment), but the durability running (running time until failure (relative value)) reached the pass level of 1.24 (b judgment), and the overall judgment was pass (C rank), confirming the reinforcing effect.

[0306] (Examples 17 and 18) In comparison with the configuration of Example 1 (R8: 20 parts by mass of first short fiber, 1 part by mass of first co-crosslinking agent), Example 17 is an example of a toothed belt in which the amount of the first short fiber contained in the first rubber layer is increased to 50 parts by mass. That is, the first rubber layer is formed of R21 (crosslinked rubber) with a tensile modulus of 9.5 MPa, and the second rubber layer is formed of R2 (crosslinked rubber) with a tensile modulus of 3.8 MPa, and the ratio of the tensile modulus of the two layers is 2.5. With regard to dynamic performance, the jumping torque (relative value) was 1.00 (b judgment), and the durability running (running time (relative value) until failure) reached the pass level of 1.30 (a judgment), and the overall judgment was pass (B rank).

[0307] Moreover, Example 18 is an example of a toothed belt in which the type of the first short fiber in Example 17 is changed to meta-aramid fiber. That is, the first rubber layer is formed of R22 (crosslinked rubber) with a tensile modulus of 10 MPa, and the second rubber layer is formed of R2 (crosslinked rubber) with a tensile modulus of 3.8 MPa, and the ratio of the tensile modulus of the two layers is 2.6. As for the dynamic performance, the jumping torque (relative value) was 1.00 (b judgment), and the durability running (running time until failure (relative value)) was 1.51 (a judgment), which reached the pass level, and the overall judgment was pass (B rank). It can be said that there is no significant difference in the reinforcing effect even if the type of short fiber is changed.

[0308] (Examples 19 to 21) In contrast to Example 3 (R10: 20 parts by mass of nylon short fiber, 6 parts by mass of first co-crosslinking agent) which had the best durability in running, Example 19 is an example of a toothed belt in which the type of the first short fiber is changed to meta-aramid fiber. That is, the first rubber layer is formed of R23 (crosslinked rubber) with a tensile modulus of 14 MPa, and the second rubber layer is formed of R2 (crosslinked rubber) with a tensile modulus of 3.8 MPa, and the ratio of the tensile modulus of the two layers is 3.7. As for dynamic performance, the jumping torque (relative value) was 1.12 (a judgment), and the durability running (running time until failure (relative value)) was 2.11 (a judgment), which reached the pass level, and the overall judgment was the same as Example 3, and passed (A rank).

[0309] Example 20 is an example of a toothed belt in which the type of the first short fiber is changed to para-aramid fiber. That is, the first rubber layer is formed of R24 (crosslinked rubber) with a tensile modulus of 14.8 MPa, and the second rubber layer is formed of R2 (crosslinked rubber) with a tensile modulus of 3.8 MPa, and the ratio of the tensile modulus of the two layers is 3.9. As for dynamic performance, the jumping torque (relative value) was 1.15 (a judgment), and the durability running (running time until failure (relative value)) was 1.39 (a judgment), which reached the pass level, and the overall judgment was pass (A rank).

[0310] Example 21 is an example of a toothed belt in which the type of the first short fiber is changed to PBO fiber. That is, the first rubber layer is formed of R25 (crosslinked rubber) with a tensile modulus of 13 MPa, and the second rubber layer is formed of R2 (crosslinked rubber) with a tensile modulus of 3.8 MPa, and the ratio of the tensile modulus of the two layers is 3.4. With regard to dynamic performance, the jumping torque (relative value) was 1.12 (a judgment), and the durability running (running time until failure (relative value)) was 1.85 (a judgment), which reached the pass level, and the overall judgment was pass (A rank).

[0311] It was confirmed that changing the type of short fiber could provide a reinforcing effect in terms of both jumping torque and running durability (longer life).

[0312] (Examples 22 to 24) This is an example in which the relationship between the area ratio of the first rubber layer to all rubber layers constituting the tooth part (hereinafter, area ratio) and the elastic modulus of the first rubber layer (the ratio of the first short fibers contained in the first rubber layer) was examined in a cross-sectional view of the tooth part. Example 22 is an example near the lower limit of the reinforcing effect (when the area ratio is small and the ratio of the first short fibers is also small), with an area ratio of 10% and 5 parts by mass of the first short fibers (tensile modulus of elasticity 10.8 MPa). Conversely, Examples 23 and 24 are examples near the upper limit of the reinforcing effect (when the area ratio is large and the ratio of the first short fibers is also large), with Example 23 having an area ratio of 60% and 50 parts by mass of the first short fibers (tensile modulus of elasticity 14 MPa), and Example 24 having an area ratio of 80% and 50 parts by mass of the first short fibers (tensile modulus of elasticity 14 MPa).

[0313] Regarding the dynamic performance, the jumping torque (relative value) was 1.00 (Example 22: judged as b), 1.28 (Example 23: judged as a), and 1.35 (Example 24: judged as a), all of which were within the acceptable level.

[0314] On the other hand, the durability running (running time until failure (relative value)) was 1.13 (Example 22: grade b), 1.28 (Example 23: grade a), and 1.05 (Example 24: grade c), all of which were within the acceptable level, and it can be said that there was a reinforcement effect.

[0315] In the overall evaluation above, the toothed belts of Examples 22 to 24 were of an acceptable standard (A to C rank).

[0316] (Examples 25 to 27, Comparative Example 9) This is an example of a toothed belt using a rubber composition having a different tensile modulus for the second rubber layer, compared to the configuration of Example 3, which had the most excellent running durability among Examples 1 to 6. That is, while Example 3 used R2 (tensile modulus of elasticity 3.8 MPa, tensile modulus ratio of two layers 3.7), Example 25 used R1 (tensile modulus of elasticity 2.4 MPa, tensile modulus ratio of two layers 5.8), Example 26 used R4 (tensile modulus of elasticity 9.4 MPa, tensile modulus ratio of two layers 1.5), Example 27 used R5 (tensile modulus of elasticity 10.9 MPa, tensile modulus ratio of two layers 1.3), and Comparative Example 9 used R7 (tensile modulus of elasticity 16.8 MPa, tensile modulus ratio of two layers 0.8) to form the second rubber layer.

[0317] Regarding dynamic performance, the jumping torque (relative value) was 1.09 (Example 25: judged as a), 1.14 (Example 26: judged as a), 1.14 (Example 27: judged as a), and 1.37 (Comparative Example 9: judged as a), all of which were within the acceptable level, and it can be said that there was a reinforcing effect.

[0318] The durability running (running time until failure (relative value)) was 1.88 (Example 25: grade a), 1.14 (Example 26: grade b), 1.08 (Example 27: grade c), and 0.42 (Comparative Example 9: grade d), which means that Examples 25 to 27 were within the acceptable level and had a reinforcing effect. On the other hand, Comparative Example 9 failed.

[0319] From the above overall judgment, the toothed belts of Examples 25 to 27 were of pass level (A to C ranks) in that they exhibited a reinforcing effect in both jumping torque and running durability. In particular, Example 25 (tensile modulus 2.4 MPa) and Example 26 (tensile modulus 9.4 MPa), in which the tensile modulus of the second rubber layer was relatively small, were of a highly pass level (A or B rank). Example 27 (tensile modulus 10.9 MPa), in which the tensile modulus of the second rubber layer was relatively large, had little effect on extending the life, and was ranked C. Furthermore, Comparative Example 9, in which the tensile modulus of the second rubber layer was increased to be greater than the tensile modulus of the first rubber layer, had a short running life and was ranked D.

[0320] (Examples 28 and 29) Examples 28 and 29 are examples of toothed belts in which the rubber composition of the first rubber layer is changed compared to Example 25, in which the second rubber layer has a relatively small tensile modulus (R1: tensile modulus 2.4 MPa). Example 28 is a toothed belt in which the first rubber layer is formed of R8 (crosslinked rubber) with a tensile modulus of 5.3 MPa, and the ratio of the tensile modulus of the two layers is 2.2. The jumping torque (relative value) was 1.02 (a judgment), and the durability running (running time until failure (relative value)) was 1.23 (b judgment), which were pass levels, and the overall judgment was pass level (B rank).

[0321] Example 29 is a toothed belt in which the first rubber layer is formed of R13 (crosslinked rubber) with a tensile modulus of 23.5 MPa, and the ratio of the tensile modulus of the two layers is 9.8. The jumping torque (relative value) was 1.16 (a rating), and the durability running (running time until failure (relative value)) was 1.24 (b rating), and the overall rating was a pass level (B rank).

[0322] (Example 30, Comparative Example 10) Example 30 and Comparative Example 10 are examples of toothed belts in which the rubber composition of the first rubber layer is changed compared to Comparative Example 9 in which the tensile modulus of the second rubber layer is relatively large (R7: tensile modulus of 16.8 MPa, ratio of tensile modulus of the two layers is 0.8). Comparative Example 10 is a toothed belt in which the first rubber layer is formed of R8 (crosslinked rubber) with a tensile modulus of 5.3 MPa and the ratio of tensile modulus of the two layers is 0.3. The jumping torque (relative value) was 1.19 (a judgment), but the durability running (running time until failure (relative value)) was 0.74 (d judgment), which was unacceptable. As in Comparative Example 9, the tensile modulus of the second rubber layer was larger than that of the first rubber layer, and the overall judgment was unacceptable (D rank).

[0323] On the other hand, Example 30 is a toothed belt in which the first rubber layer is formed of R13 (crosslinked rubber) with a tensile modulus of 23.5 MPa, and the ratio of the tensile modulus of the two layers is 1.4. The jumping torque (relative value) was 1.59 (a judgment), and the durability running (running time until failure (relative value)) was 1.01 (c judgment), which reached the pass level, and the overall judgment was pass level (C rank).

[0324] (Example 31) Example 31 is an example of a toothed belt that does not use a reinforcing inorganic filler (carbon black) compared to the configuration of Example 3 (first rubber layer R10, second rubber layer R2) that had the best durability among Examples 1 to 30. That is, the first rubber layer is an example of a toothed belt formed of a crosslinked rubber composition of R27 (tensile modulus 13.9 MPa) which is a composition obtained by removing carbon black from R10, and the second rubber layer is an example of a toothed belt formed of R26 (tensile modulus 3.8 MPa) which is a composition obtained by removing carbon black from R2. The jumping torque (relative value) was 1.10 (a judgment), and the durability running (running time (relative value) until failure) was 2.07 (a judgment), and the overall judgment was a passing level (A rank) similar to Example 3.

[0325] (Examples 32 and 33) Examples 32 and 33 are examples of toothed belts in which tooth cloth is not provided on the surfaces of the teeth and tooth bottoms of the belt, as compared with Example 3 (20 parts by mass of the first short fibers) and Example 14 (50 parts by mass of the first short fibers), respectively. Example 32 had a jumping torque (relative value) of 1.15 (a rating), and a durable running time (running time until failure (relative value)) of 2.03 (a rating), and the overall rating was a passing level (A rank) equivalent to Example 3. Example 33 had a jumping torque (relative value) of 1.10 (a rating), and a durable running time (running time until failure (relative value)) of 1.29 (a rating), and the overall rating was a passing level (A rank) equivalent to Example 14.

[0326] From the above results, it was confirmed that a belt made of a first rubber layer formed along the tooth cloth and a second rubber layer formed between this first rubber layer and the core wire, with the elastic modulus of the first rubber layer being adjusted to be greater than that of the second rubber layer, and short fibers being blended into the first rubber layer so that they are oriented in the longitudinal direction of the belt along the contour of the tooth portion, makes it possible to achieve a balance between the rigidity and flexibility of the tooth portion, which are in a contradictory relationship, and suppresses jumping (tooth skipping) while the belt is running, as well as preventing tooth loss (tooth chipping), thereby enabling the belt to be adapted to a longer life during high-load running.

[0327] Examples 34 to 44 and Comparative Example 11 [Manufacturing of toothed belts] In Examples 34 to 44 and Comparative Example 11, as shown below, using the preforming method described in this embodiment, toothed belts having a total thickness of 7.0 mm, tooth type G8M, tooth height (including tooth cloth) of 3.5 mm, tooth pitch 8 mm, number of teeth 140, circumference length 1120 mm, and width 17 mm were produced.

[0328] For the toothed belts produced in Examples 34 to 44 and Comparative Example 11, the configurations (layer structures) of the toothed portions, the rubber compositions used in each rubber layer, and the twisted cords used in the core wires are shown in Table 13.

[0329] Comparative Example 11 A tooth cloth precursor for forming the tooth cloth and an uncrosslinked rubber sheet (R28, sheet thickness 1.70 mm) for forming the rubber layer of the tooth portion were laminated in that order on a press mold (flat) having multiple grooves (concave strips) corresponding to the teeth of the toothed belt, and pressed for 160 seconds under conditions of a temperature of 90°C and a pressing pressure (surface pressure) of 20.2 MPa to produce a semi-crosslinked preform.

[0330] Next, the preform was wound around a cylindrical mold having a plurality of grooves (concave stripes) corresponding to the teeth and attached (the teeth and grooves were engaged), and the twisted cord constituting the core wire shown in Table 13 was spun helically on the outer circumferential surface of the preform under the conditions shown in Table 13 (tension: 150-250 N / piece, spinning pitch: 1.15 mm, spinning speed: 1.5 m / s). Furthermore, an uncrosslinked rubber sheet (R30, sheet thickness 0.90 mm) forming the back rubber layer was wound around the outer circumferential side to form an uncrosslinked belt molded body (uncrosslinked laminate). The uncrosslinked rubber sheet was wound so that the orientation direction of the short fibers contained in the sheet was the belt longitudinal direction.

[0331] Next, crosslinking molding was carried out for 40 minutes using a vulcanizer under conditions of a heating temperature of 179° C. and a steam pressure of 0.83 MPa to produce a crosslinked molded product (crosslinked belt sleeve).

[0332] Finally, the crosslinked belt sleeve was removed from the cylindrical mold and cut to a width of 17 mm to obtain a toothed belt.

[0333] (Examples 34 to 44) Two types of uncrosslinked rubber sheets forming the rubber layers of the toothed portion were laminated in this order, an uncrosslinked rubber sheet (R16, sheet thickness 0.70 mm) forming the first rubber layer and an uncrosslinked rubber sheet (R29, sheet thickness 1.00 mm) forming the second rubber layer, and toothed belts were produced in the same manner as in Comparative Example 11, except that the core wires shown in Table 13 were spun under the conditions shown in Table 13. In each of the toothed belts, the area ratio of the first rubber layer to all rubber layers constituting the toothed portion was 40%.

[0334] [Belt elasticity] The belt elastic modulus (tensile elastic modulus) was measured under conditions of room temperature of 23±2° C. and humidity of 50±5%. More specifically, the test belt was left under the same conditions for 24 hours or more and then measured by the following method.

[0335] First, a pair of toothed pulleys (20 teeth) was attached to the lower fixed part and the upper load cell connecting part of the autograph [Shimadzu Corporation "AGS-J10kN"], and a toothed belt (test belt) was hung between the pulleys. Next, the upper pulley was raised, and an initial tension T0 (for example, about 5N for a toothed belt with a belt width of 10 mm) was applied to the toothed belt to such an extent that the longitudinal deflection of the toothed belt was removed. In this state, the position of the upper pulley was set to the initial position, the belt circumference was set to the belt reference circumference (L0) (mm), and the belt length change rate (dimensionless) was set to 0 (origin), and the upper pulley was raised at a speed of 10 mm / min, and the relationship (SS diagram) between the belt length change rate (dimensionless) (horizontal axis) and the belt tension (N) (vertical axis) was recorded on a PC (personal computer). The belt length change rate (dimensionless) on the horizontal axis is equal to the center distance change rate (dimensionless) between the pulleys. The belt tension (N) on the vertical axis is the value obtained by dividing the axial load (N) corresponding to the load detected by the load cell of the tensile tester (autograph) by 2.

[0336] The belt elasticity EA per full width of the test belt within a specified range of mounting tension corresponds to the slope of an approximate straight line connecting two points P1 and P2, where L1 is the belt circumference (mm) when the belt is stretched to the belt tension T1 (N) corresponding to the lower limit of the mounting tension, P1 is the passing point on the SS diagram at that time, L2 is the belt circumference (mm) when the belt is stretched to the belt tension T2 (N) corresponding to the upper limit of the mounting tension, and P2 is the passing point on the SS diagram at that time. The increase (T2-T1) (N) in the belt tension T (N) between P1 and P2 was divided by the belt length change rate [(L2-L1) / L1] (dimensionless) between P1 and P2 to calculate the value (N) (corresponding to the so-called "tensile stiffness of the belt"), and this value was converted per 1 mm of belt width to be the belt elasticity modulus (N / mm).

[0337] In this application, the belt elastic modulus was measured within the above mounting tension range (T1 to T2), which is 10 to 60 kN / mm per 1 mm of belt width for belts with a tooth pitch of 8 mm, 20 to 100 kN / mm for belts with a tooth pitch of 11 mm, and 50 to 175 kN / mm for belts with a tooth pitch of 14 mm.

[0338] The belt elastic modulus can also be expressed in units of (N / %). In this case, the horizontal axis of the SS diagram is not the value (dimensionless) of the belt length change rate [(L2-L1) / L1], but the percentage (%) of the belt length change rate [(L2-L1) / L1] (so-called "belt elongation rate (%)"). Multiplying the value of the belt elastic modulus (N / %) by 100 can be converted into the value (N) of the belt elastic modulus EA defined in this application.

[0339] [Jumping test] (Driving test conditions) Using a two-axis torque measuring tester, a toothed belt was wound between a driving pulley (number of teeth: 24) and a driven pulley (number of teeth: 59), and the center distance of the pulleys was adjusted so that the belt tension was 400N.The driving pulley was then rotated at 1,200 rpm to run the belt while continuously increasing the load on the driven pulley, and the load torque applied to the driven pulley when jumping (tooth skipping) occurred was measured as the jumping torque.The jumping torque value is used as an index of jumping resistance, and the higher the jumping torque value, the better the toothed belt is, as it is less prone to tooth skipping.

[0340] The jumping torque value of each example is shown converted into a relative value, with the jumping torque value (250 N m) of Comparative Example 11 taken as 1.00. A value of 1.00 or less indicates that there is no reinforcing effect for the toothed belt of Comparative Example 11, whereas a value exceeding 1.00 indicates that the stiffness (resistance to deformation) of the teeth has been improved by the reinforcing effect. The higher this value, the greater the reinforcing effect.

[0341] (Jumping test criteria) A: Jumping torque exceeds 1.10 (pass) b: Jumping torque is over 1.00 and below 1.10 (pass) c: Jumping torque is 1.00 (fail) d: Jumping torque is less than 1.00 (fail).

[0342] [Durability test] (Driving test conditions) The toothed belt was attached to a biaxial running test machine equipped with a drive pulley (number of teeth: 24) and a driven pulley (number of teeth: 59), and the running life was measured as the running time until the toothed belt failed (loss of teeth). The installation tension of the toothed belt was 400 N, the rotation speed of the drive pulley was 1000 rpm, the load on the driven pulley was 283 N m, and the ambient temperature was 25°C (room temperature).

[0343] With regard to the rate at which tension is maintained after 100 hours of running relative to the initial tension (hereinafter referred to as "tension maintenance rate"), if it exceeds 50%, it indicates that the reinforcement effect is suppressing belt elongation due to a decrease in tension, and the higher this value, the more highly the reinforcement effect is exerted.

[0344] (Criteria for determining tension maintenance rate) A: Tension retention rate after 100 hours is 80% or more of the initial value (pass) b: Tension retention rate after 100 hours is 70% or more and less than 80% of the initial value (pass) c: Tension retention rate after 100 hours is more than 50% and less than 70% of the initial value (pass) d: Tension retention after 100 hours is less than 50% of the initial value (fail).

[0345] In addition, the running time until failure (hereinafter referred to as "lifetime") is shown as a relative value, with the running time of Comparative Example 11 (241 hours) set to 1.00, and the running time of each Example is shown as a relative value. If this value is 1.00 or less, it indicates that the reinforcing effect for the toothed belt of Comparative Example 11 is not exhibited, and if it exceeds 1.00, it indicates that the reinforcing effect has improved the running durability, and it can be said that the higher this value is, the higher the reinforcing effect is exhibited.

[0346] (Criteria for determining life time) A: The running time until failure is 1.25 or more (pass) b: Run time to failure is 1.10 or more and less than 1.25 (pass) c: Run time to failure is greater than 1.00 and less than 1.10 (pass) d: Run time to failure is less than 1.00 (fail).

[0347] [Overall Judgment] Taking into consideration the level of reinforcement effect in terms of jumping torque in the jumping test, tension retention rate in the durability running test, and life time, the overall superiority was judged (ranked) according to the following criteria. From the viewpoint of practicality of the product, A, B, and C ranks were considered to be acceptable, and D rank was considered to be unacceptable.

[0348] Rank A: All three tests above are rated A Rank B: Includes b grades in the above three tests (does not include c or d grades) Rank C: Includes C grades in the above three tests (does not include D grades) Rank D: Includes a rating of d in the three tests above.

[0349] Regarding the toothed belts of Examples 34 to 44 and Comparative Example 11, the verification results are shown in Table 13.

[0350] [Table 13]

[0351] (Examples 37 to 41) In Examples 37 to 41, in the toothed belts having teeth with a specific double-layer structure, the cord diameter D, pitch P, and arrangement density X of the cord were adjusted to specific ranges, and therefore the belt elastic modulus was within an appropriate range, so that the jumping resistance and running durability required for power transmission applications in rear-wheel drive of motorcycles were excellent, and the overall evaluation was rank A or B. In particular, Examples 37 to 40, in which the cord pitch P was 1.10 to 1.15 mm, were ranked A.

[0352] Comparative Example 11 In Comparative Example 11, the entire rubber layer of the tooth portion has a single-layer structure and the belt elastic modulus is low at 14.7 kN / mm. However, the jumping resistance and tension retention rate were low, and the life time was also short, so the overall evaluation was ranked D.

[0353] (Examples 34 to 36 and 42 to 44) Example 34 is an example in which the core wire diameter D is 0.7 mm and the core wire pitch P is 0.85 mm, which are small, so the belt elastic modulus is high at 22.2 kN / mm. However, compared to Examples 37 to 41, the tension retention rate is low and the life time is short, so the overall evaluation was rank C.

[0354] In Example 35, the X value of the cord arrangement density was low at 4.76%, so the belt elastic modulus was low at 13.4 kN / mm. However, compared with Examples 37 to 41, the life time was short, so the overall evaluation was given a rank of C.

[0355] Example 36 is an example in which the twist factor of the core wire is low at 0.94, but compared with Examples 37 to 41, the life time was short, and therefore the overall evaluation was given a rank of C.

[0356] Example 42 is an example in which the cord twist factor is high at 2.21 and the belt elastic modulus is low at 14.0 kN / mm, but compared with Examples 37 to 41, the life time was short, and therefore the overall evaluation was given a C rank.

[0357] In Example 43, the X value of the cord arrangement density was high at 25.93%, and therefore the belt elastic modulus was high at 21.4 kN / mm. However, compared with Examples 37 to 41, the life time was short, and therefore the overall evaluation was given a rank of C.

[0358] Example 44 is an example in which the core wire diameter D is large at 1.3 mm, and therefore the belt elastic modulus is low at 13.8 kN / mm. However, compared to Examples 37 to 41, the tension retention rate is low and the life time is short, so the overall evaluation was rank C.

[0359] From these results, particularly suitable ranges of the core wire and belt elastic modulus for a toothed belt of tooth type G8M with a tooth pitch of 8 mm are summarized in Table 14.

[0360] [Table 14]

[0361] Examples 45 to 57 and Comparative Example 12 [Manufacturing of toothed belts] In Examples 45 to 57 and Comparative Example 12, as shown below, using the preforming method described in this embodiment, toothed belts having a total thickness of 8.5 mm, a tooth profile H of 11M, a tooth height (including tooth cloth) of 5.1 mm, a tooth pitch of 11 mm, a number of teeth of 113, a circumference of 1243 mm, and a width of 25 mm were produced.

[0362] For the toothed belts produced in Examples 45 to 57 and Comparative Example 12, the configurations (layer structures) of the toothed portions, the rubber compositions used in each rubber layer, and the twisted cords used in the core wires are shown in Table 15.

[0363] Comparative Example 12 A tooth cloth precursor for forming the tooth cloth and an uncrosslinked rubber sheet (R28, sheet thickness 2.7 mm) for forming the rubber layer of the tooth portion were laminated in that order on a press mold (flat) having multiple grooves (concave strips) corresponding to the teeth of the toothed belt, and pressed for 160 seconds under conditions of a temperature of 90°C and a pressing pressure (surface pressure) of 20.2 MPa to produce a semi-crosslinked preform.

[0364] Next, the preform was wound around a cylindrical mold having a plurality of grooves (concave stripes) corresponding to the teeth and attached (the teeth and grooves were engaged), and the twisted cords constituting the core wires shown in Tables 15 and 16 were spun helically on the outer circumferential surface of the preform under the conditions shown in Tables 15 and 16 (tension: 250-600 N / piece, spinning pitch: 2.20 mm, spinning speed: 1.5 m / s). Furthermore, an uncrosslinked rubber sheet (R30, sheet thickness 1.3 mm) forming the back rubber layer was wound around the outer circumferential side to form an uncrosslinked belt molded body (uncrosslinked laminate). The uncrosslinked rubber sheet was wound so that the orientation direction of the short fibers contained in the sheet was the belt longitudinal direction.

[0365] Next, crosslinking molding was carried out for 40 minutes using a vulcanizer under conditions of a heating temperature of 179° C. and a steam pressure of 0.83 MPa to produce a crosslinked molded product (crosslinked belt sleeve).

[0366] Finally, the crosslinked belt sleeve was removed from the cylindrical mold and cut to a width of 25 mm to obtain a toothed belt.

[0367] (Examples 45 to 57) Toothed belts were produced in the same manner as in Comparative Example 12, except that two types of uncrosslinked rubber sheets forming the rubber layers of the toothed portion were laminated in this order, an uncrosslinked rubber sheet (R16, sheet thickness 1.1 mm) forming the first rubber layer and an uncrosslinked rubber sheet (R29, sheet thickness 1.6 mm) forming the second rubber layer, and the core wires shown in Tables 15 and 16 were spun under the conditions shown in Tables 15 and 16. In each of the toothed belts, the area ratio of the first rubber layer to all the rubber layers constituting the toothed portion was 40%.

[0368] [Belt elasticity] The belt elastic modulus was measured in the same manner as in Examples 34 to 44 and Comparative Example 11.

[0369] [Jumping test] (Driving test conditions) Using a two-axis torque measuring tester, a toothed belt was wound between a driving pulley (number of teeth: 26) and a driven pulley (number of teeth: 59), and the center distance of the pulleys was adjusted so that the belt tension was 200N.The driving pulley was then rotated at 1,200 rpm to run the belt while continuously increasing the load on the driven pulley, and the load torque applied to the driven pulley when jumping (tooth skipping) occurred was measured as the jumping torque.The jumping torque value is used as an index of jumping resistance, and the higher the jumping torque value, the better the toothed belt is, as it is less prone to tooth skipping.

[0370] The jumping torque value of each Example is shown converted into a relative value, with the jumping torque value (700 N m) of Comparative Example 12 taken as 1.00. A value of 1.00 or less indicates that the reinforcing effect for the toothed belt of Comparative Example 12 is not observed, whereas a value exceeding 1.00 indicates that the stiffness (resistance to deformation) of the teeth has been improved by the reinforcing effect, and the higher this value, the greater the reinforcing effect.

[0371] (Jumping test criteria) A: Jumping torque exceeds 1.10 (pass) b: Jumping torque is over 1.00 and below 1.10 (pass) c: Jumping torque is 1.00 (fail) d: Jumping torque is less than 1.00 (fail).

[0372] [Durability test] (Driving test conditions) The toothed belt was attached to a biaxial running test machine equipped with a drive pulley (number of teeth: 26) and a driven pulley (number of teeth: 59), and the running life was measured as the running time until the toothed belt failed (loss of teeth). The installation tension of the toothed belt was 1000 N, the rotation speed of the drive pulley was 1200 rpm, the load on the driven pulley was 668 N m, and the ambient temperature was 25°C (room temperature).

[0373] With regard to the rate at which tension is maintained after 100 hours of running relative to the initial tension (hereinafter referred to as "tension maintenance rate"), if it exceeds 50%, it indicates that the reinforcement effect is suppressing belt elongation due to a decrease in tension, and the higher this value, the more highly the reinforcement effect is exerted.

[0374] (Criteria for determining tension maintenance rate) A: Tension retention rate after 100 hours is 80% or more of the initial value (pass) b: Tension retention rate after 100 hours is 70% or more and less than 80% of the initial value (pass) c: Tension retention rate after 100 hours is more than 50% and less than 70% of the initial value (pass) d: Tension retention after 100 hours is less than 50% of the initial value (fail).

[0375] In addition, the running time until failure (hereinafter referred to as "lifetime") is shown as a relative value, with the running time of Comparative Example 12 (490 hours) set to 1.00, and the running time of each Example is shown. If this value is 1.00 or less, it indicates that the reinforcing effect for the toothed belt of Comparative Example 12 is not exhibited, and if it exceeds 1.00, it indicates that the reinforcing effect has improved the running durability, and it can be said that the higher this value is, the higher the reinforcing effect is exhibited.

[0376] (Criteria for determining life time) A: The running time until failure is 1.25 or more (pass) b: Run time to failure is 1.10 or more and less than 1.25 (pass) c: Run time to failure is greater than 1.00 and less than 1.10 (pass) d: Run time to failure is less than 1.00 (fail).

[0377] [Overall Judgment] Taking into consideration the level of reinforcement effect in terms of jumping torque in the jumping test, tension retention rate in the durability running test, and life time, the overall superiority was judged (ranked) according to the following criteria. From the viewpoint of practicality of the product, A, B, and C ranks were considered to be acceptable, and D rank was considered to be unacceptable.

[0378] Rank A: All three tests above are rated A Rank B: Includes b grades in the above three tests (does not include c or d grades) Rank C: Includes C grades in the above three tests (does not include D grades) Rank D: Includes a rating of d in the three tests above.

[0379] Regarding the toothed belts of Examples 45 to 57 and Comparative Example 12, the verification results are shown in Tables 15 and 16.

[0380] [Table 15]

[0381] [Table 16]

[0382] (Examples 45 to 50) In Examples 45 to 50, the toothed belts having teeth with a specific two-layer structure had the cord diameter D, pitch P, and arrangement density X of the cord adjusted to specific ranges, and therefore had an appropriate range of belt elasticity, and therefore had excellent jumping resistance and durable running performance required for transmission applications in rear-wheel drive motorcycles, and were comprehensively judged to be ranks A to B. Among them, Examples 45 and 48 to 49 were comprehensively judged to be rank A, which was particularly good.

[0383] Example 51 is an example in which the cord twist coefficient is higher at 2.92 and the belt elastic modulus is lower at 40.8 kN / mm than Examples 48 and 49, but the tension retention rate is lower than Examples 45 to 50, and the overall evaluation was graded C.

[0384] Comparative Example 12 In Comparative Example 12, the entire rubber layer of the tooth portion has a single-layer structure, the core wire has a high upper twist coefficient of 3.01, and the core wire diameter D and core wire pitch P are all large at 2.0 and 2.20, respectively, resulting in a low belt elastic modulus of 40.8 kN / mm. However, the jumping resistance (jumping torque) and tension retention rate were low, and the life span was also short, resulting in an overall rating of D rank.

[0385] (Examples 52 to 57) Example 52 is an example in which the core wire upper twist coefficient is high at 3.01, the core wire diameter D is 2.0, and the core wire pitch P is 2.20, all of which are large, resulting in a low belt elastic modulus of 40.8 kN / mm. However, compared to Examples 45 to 50, the tension retention rate was low and the life time was short, so the overall assessment was rank C.

[0386] Example 53 is an example in which the core wire diameter D is small at 1.0 mm and the core wire arrangement density X value is high at 28.57%, resulting in a low belt elastic modulus of 18.5 kN / mm. However, compared with Examples 45 to 50, the jumping resistance was low and the life time was short, resulting in an overall rating of C rank.

[0387] Example 54 is an example in which the cord twist coefficient is high at 3.01 and the belt elastic modulus is low at 34.4 kN / mm, but compared with Examples 45 to 50, the life time was short, and the overall evaluation was given a C rank.

[0388] Example 55 is an example in which the X value of the arrangement density of the core wires is low at 2.70%, but compared with Examples 45 to 50, the life time was short, and therefore the overall evaluation was given a C rank.

[0389] Example 56 is an example in which the core wire pitch P is large at 2.10 mm and the belt elastic modulus is high at 54.6 kN / mm. However, compared to Examples 45 to 50, it had lower jumping resistance and a shorter life span, and was therefore given an overall rating of C rank.

[0390] Example 57 is an example in which the core wire diameter D is 2.1 mm, the core wire pitch P is 2.20 mm, both of which are large, and the core wire arrangement density X value is 4.55%, but compared to Examples 45 to 50, the life time was short, and the overall evaluation was rank C.

[0391] From these results, the appropriate ranges of the core wire and belt elastic modulus for a toothed belt of tooth type H11M with a tooth pitch of 11 mm are summarized in Table 17.

[0392] [Table 17]

[0393] Examples 58 to 75 and Comparative Example 13 [Manufacturing of toothed belts] In Examples 58 to 75 and Comparative Example 13, as shown below, using the preforming method described in this embodiment, toothed belts having a total thickness of 10.6 mm, a tooth profile H of 14M, a tooth height (including tooth cloth) of 6.2 mm, a tooth pitch of 14 mm, a number of teeth of 144, a circumference of 2016 mm, and a width of 21 mm were produced.

[0394] For the toothed belts produced in Examples 58 to 75 and Comparative Example 13, the configurations (layer structures) of the toothed portions, the rubber compositions used in each rubber layer, and the twisted cords used in the core wires are shown in Tables 18 to 20.

[0395] Comparative Example 13 A tooth cloth precursor for forming the tooth cloth and an uncrosslinked rubber sheet (R28, sheet thickness 2.9 mm) for forming the rubber layer of the tooth portion were laminated in that order on a press mold (flat) having multiple grooves (concave strips) corresponding to the teeth of the toothed belt, and pressed for 160 seconds under conditions of a temperature of 90°C and a press pressure (surface pressure) of 20.2 MPa to produce a semi-crosslinked preform.

[0396] Next, the preform was wound around a cylindrical mold having a plurality of grooves (concave strips) corresponding to the teeth and attached (the teeth and grooves were engaged), and the twisted cord constituting the core wire shown in Table 19 was spun helically on the outer circumferential surface of the preform under the conditions shown in Table 19 (tension: 450 to 750 N / piece, spinning pitch: 2.20 mm, spinning speed: 1.5 m / s). Further, an uncrosslinked rubber sheet (R30, sheet thickness 2.0 mm) forming the back rubber layer was wound around the outer circumferential side to form an uncrosslinked belt molded body (uncrosslinked laminate). The uncrosslinked rubber sheet was wound so that the orientation direction of the short fibers contained in the sheet was the belt longitudinal direction.

[0397] Next, crosslinking molding was carried out for 40 minutes using a vulcanizer under conditions of a heating temperature of 179° C. and a steam pressure of 0.83 MPa to produce a crosslinked molded product (crosslinked belt sleeve).

[0398] Finally, the crosslinked belt sleeve was removed from the cylindrical mold and cut to a width of 21 mm to obtain a toothed belt.

[0399] (Examples 58 to 75) Toothed belts were produced in the same manner as in Comparative Example 13, except that two types of uncrosslinked rubber sheets forming the rubber layers of the toothed portion were laminated in this order, an uncrosslinked rubber sheet (R16, sheet thickness 1.2 mm) forming the first rubber layer and an uncrosslinked rubber sheet (R29, sheet thickness 1.7 mm) forming the second rubber layer, and the core wires shown in Tables 18 to 20 were spun under the conditions shown in Tables 18 to 20. In each of the toothed belts, the area ratio of the first rubber layer to all the rubber layers constituting the toothed portion was 40%.

[0400] [Belt elasticity] The belt elastic modulus was measured in the same manner as in Examples 34 to 44 and Comparative Example 11.

[0401] [Jumping test] (Driving test conditions) Using a two-axis torque measuring tester, a toothed belt was wound between a driving pulley (number of teeth: 33) and a driven pulley (number of teeth: 61), and the center distance of the pulleys was adjusted so that the belt tension was 200N.The driving pulley was then rotated at 1,200 rpm to run the belt while continuously increasing the load on the driven pulley, and the load torque applied to the driven pulley when jumping (tooth skipping) occurred was measured as the jumping torque.The jumping torque value is used as an index of jumping resistance, and the higher the jumping torque value, the better the toothed belt is, as it is less likely to skip teeth.

[0402] The jumping torque value of each example is shown converted into a relative value, with the jumping torque value (540 N m) of Comparative Example 13 taken as 1.00. A value of 1.00 or less indicates that there is no reinforcing effect for the toothed belt of Comparative Example 13, whereas a value exceeding 1.00 indicates that the stiffness (resistance to deformation) of the teeth has been improved by the reinforcing effect. The higher this value, the greater the reinforcing effect.

[0403] (Jumping test criteria) A: Jumping torque exceeds 1.10 (pass) b: Jumping torque is over 1.00 and below 1.10 (pass) c: Jumping torque is 1.00 (fail) d: Jumping torque is less than 1.00 (fail).

[0404] [Durability test] (Driving test conditions) The toothed belt was attached to a biaxial running test machine equipped with a drive pulley (number of teeth: 33) and a driven pulley (number of teeth: 61), and the running life was measured as the running time until the toothed belt failed (loss of teeth). The installation tension of the toothed belt was 1150 N, the rotation speed of the drive pulley was 1200 rpm, the load on the driven pulley was 910 N m, and the ambient temperature was 25°C (room temperature).

[0405] Regarding the rate at which the tension is maintained after 100 hours of running compared to the initial tension (hereinafter referred to as tension maintenance rate), if it exceeds 50%, it indicates that the reinforcement effect is suppressing belt elongation due to a decrease in tension, and the higher this value, the more highly the reinforcement effect is exerted.

[0406] (Criteria for determining tension maintenance rate) A: Tension retention rate after 100 hours is 80% or more of the initial value (pass) b: Tension retention rate after 100 hours is 70% or more and less than 80% of the initial value (pass) c: Tension retention rate after 100 hours is more than 50% and less than 70% of the initial value (pass) d: Tension retention after 100 hours is less than 50% of the initial value (fail).

[0407] In addition, the running time until failure (hereinafter, life time) is shown as a relative value, with the running time of Comparative Example 13 (506 hours) set to 1.00, and the running time of each Example is shown as a relative value. If this value is 1.00 or less, it indicates that the reinforcing effect for the toothed belt of Comparative Example 13 is not exhibited, and if it exceeds 1.00, it indicates that the reinforcing effect has improved the running durability, and it can be said that the higher this value is, the higher the reinforcing effect is exhibited.

[0408] (Criteria for determining life time) A: The running time until failure is 1.25 or more (pass) b: Run time to failure is 1.10 or more and less than 1.25 (pass) c: Run time to failure is greater than 1.00 and less than 1.10 (pass) d: Run time to failure is less than 1.00 (fail).

[0409] [Overall Judgment] Taking into consideration the level of reinforcement effect in terms of jumping torque in the jumping test, tension retention rate in the durability running test, and life time, the overall superiority was judged (ranked) according to the following criteria. From the viewpoint of practicality of the product, A, B, and C ranks were considered to be acceptable, and D rank was considered to be unacceptable.

[0410] Rank A: All three tests above are rated A Rank B: Includes b grades in the above three tests (does not include c or d grades) Rank C: Includes C grades in the above three tests (does not include D grades) Rank D: Includes a rating of d in the three tests above.

[0411] Regarding the toothed belts of Examples 58 to 75 and Comparative Example 13, the verification results are shown in Tables 18 to 20.

[0412] [Table 18]

[0413] [Table 19]

[0414] [Table 20]

[0415] (Examples 58 to 64) In Examples 58 to 64, the core wire diameter D, pitch P, and arrangement density X of the core wire were adjusted to a specific range in the toothed belt having a tooth portion with a specific double-layer structure, and the belt elastic modulus was within an appropriate range, so that the jumping resistance and running durability required for transmission applications in rear-wheel drive of motorcycles were excellent, and the overall evaluation was A to B rank. Among them, Examples 58 to 60 and 64 were especially good, with an overall evaluation of A rank. Note that Example 64 uses a smaller diameter core wire (3-strand 12K-1 / 3) than Examples 58 to 60, but by adjusting the arrangement density of the core wire to be larger (X to be smaller), the life time was improved compared to Examples 58 to 60, and was evaluated as A rank.

[0416] Comparative Example 13 In Comparative Example 13, the entire rubber layer of the tooth portion has a single-layer structure, and the core wire has a high upper twist coefficient of 2.65, so the belt elastic modulus is low at 49.8 kN / mm. However, the jumping resistance and tension retention rate were low, and the life time was also short, so the overall evaluation was rank D.

[0417] (Examples 65 to 69) Example 65 is an example in which the belt elastic modulus is low at 49.8 kN / mm due to the high core wire twist coefficient of 2.65. However, compared to Examples 58 to 64, the tension retention rate is low and the life time is short, so the overall evaluation was rank C.

[0418] Example 66 is an example in which the core wire twist coefficient is high at 3.06, the core wire diameter D is small at 1.7 mm, and the core wire pitch P is small at 1.90 mm, resulting in a low belt elastic modulus of 49.5 kN / mm. However, compared to Examples 58 to 64, the tension retention rate was low and the life time was short, so the overall evaluation was rank C.

[0419] Example 67 is an example in which the belt elastic modulus is low at 49.2 kN / mm due to a small cord diameter D of 1.8 mm, but compared with Examples 58 to 64, the life time was short, and therefore the overall evaluation was given a C rank.

[0420] In Example 68, the X value of the cord arrangement density was high at 25.93%, and therefore the belt elastic modulus was low at 47.4 kN / mm. However, compared to Examples 58 to 64, the tension retention rate was low and the life time was short, so the overall evaluation was ranked C.

[0421] Example 69 is an example in which the core wire diameter D is 2.5 mm and the core wire pitch P is 2.70 mm, which are large, but compared with Examples 58 to 64, the life time was short, and therefore the overall evaluation was given a C rank.

[0422] (Examples 70 to 75) In Example 64, which used a thin core wire, this is an example in which the combination of rubber compositions was changed. The core wire diameter D, pitch P, and arrangement density X of the core wire were adjusted within specific ranges, and the belt elastic modulus was within an appropriate range. As a result, the belt had excellent jumping resistance, tension retention, and running durability required for transmission applications in rear-wheel drive motorcycles, and was overall judged to be Rank A.

[0423] From these results, the appropriate ranges of the core wire and belt elastic modulus for a toothed belt of tooth type H14M with a tooth pitch of 14 mm are summarized in Table 21.

[0424] [Table 21] [Industrial Applicability]

[0425] The toothed belt (meshing power transmission belt or toothed power transmission belt) of the present invention can be used in combination with a toothed pulley in various fields where synchronization between input and output is required, for example, power transmission mechanisms in vehicles such as automobiles and motorcycles, power transmission mechanisms in motors and pumps of industrial machines, machinery such as automatic doors and automated machines, copiers, printers, etc. In particular, it can be used as a power transmission belt (timing belt or toothed belt) for industrial machines for high load (high horsepower) applications and rear wheel drive of motorcycles. [Explanation of symbols]

[0426] 1...Toothed belt 1a...teeth part 1b…Tooth bottom 1c...back 2…Tooth cloth 3…First rubber layer 3a…First short fiber 4...Second rubber layer 5…Core wire 6…Back rubber layer

Claims

1. A toothed belt for use in power transmission in rear-wheel drive of a motorcycle, comprising: A back portion in which a core wire extending along a circumferential direction of the belt is embedded; A plurality of teeth are formed on an inner circumferential surface of the back portion at intervals in a belt circumferential direction, A toothed belt including a back rubber layer formed on the outer circumferential side of the belt with respect to the core wire, and a first rubber layer and a second rubber layer formed on the inner circumferential side of the belt with respect to the core wire, The back portion includes the back rubber layer, the elastic modulus of the first rubber layer is greater than the elastic modulus of the second rubber layer, the first rubber layer is formed of a first crosslinked rubber composition containing a first rubber component and first short fibers, a ratio of the first short fibers is 20 to 60 parts by mass with respect to 100 parts by mass of the first rubber component, The first short fibers are oriented in the belt longitudinal direction along the contour of the tooth portion, the core wire comprises high modulus fibers, The X value of the arrangement density of the core wire is 5 to 25%, and The toothed belt, wherein the tooth portion includes the first rubber layer and the second rubber layer interposed between the first rubber layer and the core wire.

2. 2. The toothed belt according to claim 1, wherein an area ratio of the first rubber layer to a total area of ​​the first rubber layer and the second rubber layer is 10 to 80% in a cross section seen in a circumferential direction of the belt.

3. The first rubber layer has a tensile strength in a circumferential direction of the belt of 40 to 90 MPa, the first rubber layer has a tensile modulus in the belt width direction of 4 to 25 MPa; The second rubber layer has a tensile strength in the circumferential direction of the belt of 10 to 50 MPa, and 3. The toothed belt according to claim 1, wherein the second rubber layer has a tensile modulus of elasticity in the belt width direction of 1 to 10 MPa.

4. 3. The toothed belt according to claim 1, wherein the tensile modulus of elasticity in the belt width direction of the first rubber layer is 1.1 to 10 times the tensile modulus of elasticity in the belt width direction of the second rubber layer.

5. 3. The toothed belt according to claim 1, wherein the first short fibers are polyamide fibers.

6. The first crosslinked rubber composition further comprises a first crosslinking agent and a first co-crosslinking agent, the second rubber layer is formed of a second crosslinked rubber composition containing a second rubber component, a second crosslinking agent, and a second co-crosslinking agent; The first rubber component includes a first composite polymer including a hydrogenated nitrile rubber and an unsaturated carboxylic acid metal salt, The second rubber component includes a second composite polymer including a hydrogenated nitrile rubber and an unsaturated carboxylic acid metal salt, A ratio of the first co-crosslinking agent is 1 to 40 parts by mass with respect to 100 parts by mass of the first rubber component, and 3. The toothed belt according to claim 1, wherein a ratio of the second co-crosslinking agent is 0.2 to 25 parts by mass with respect to 100 parts by mass of the second rubber component.

7. 7. The toothed belt according to claim 6, wherein the second crosslinked rubber composition further contains second short fibers, and a ratio of the second short fibers in the second crosslinked rubber composition is 5 parts by mass or less per 100 parts by mass of the second rubber component.

8. The first crosslinked rubber composition further comprises a first reinforcing inorganic filler, The second crosslinked rubber composition further comprises a second reinforcing inorganic filler, A ratio of the first composite polymer in the first rubber component is 80% by mass or more, A ratio of the second composite polymer in the second rubber component is 30% by mass or more, the first crosslinking agent contains a first organic peroxide, and a ratio of the first organic peroxide is 1 to 20 parts by mass with respect to 100 parts by mass of the first rubber component; the second crosslinking agent contains a second organic peroxide, and a ratio of the second organic peroxide is 0.5 to 5 parts by mass with respect to 100 parts by mass of the second rubber component, a ratio of the first reinforcing inorganic filler is 10 parts by mass or less based on 100 parts by mass of the first rubber component; and 7. The toothed belt according to claim 6, wherein a ratio of the second reinforcing inorganic filler is 10 parts by mass or less per 100 parts by mass of the second rubber component.

9. The tooth pitch of the tooth portion is 6 to 16 mm, When the tooth pitch is 6 mm or more and less than 9.5 mm, the belt elastic modulus is 15 to 20 kN / mm; When the tooth pitch is 9.5 mm or more and less than 12.5 mm, the belt elastic modulus is 42 to 60 kN / mm; and 3. The toothed belt according to claim 1, wherein the belt elasticity modulus is 50 to 65 kN / mm when the tooth pitch is 12.5 to 16 mm.

10. 3. A toothed belt transmission mechanism comprising the toothed belt according to claim 1 or 2 and a pulley, the toothed belt being used for power transmission in rear wheel drive of a motorcycle.

11. 3. A method for producing a toothed belt according to claim 1 or 2, comprising: a first-rubber-layer-preparing step of preparing an uncrosslinked rubber sheet having first short fibers oriented in one direction of the sheet surface as a first-rubber-layer precursor for forming the first rubber layer; and a preforming step of laminating the first rubber layer precursor and a second rubber layer precursor, which is an uncrosslinked rubber sheet for forming the second rubber layer, in an arrangement in which the first short fibers are oriented in the belt longitudinal direction, to produce a preform in a semi-crosslinked state.

Citation Information

Patent Citations

  • Core wire for driving belt and driving belt using the same

    JP2003148563A

  • Toothed belt transmission device

    JP2021188747A

  • Transmission belt

    JP2022109878A

  • Toothed belt

    JP2022160370A

  • Toothed belt and manufacturing method therefor

    JP2023018654A